Semiconductor nanoparticle, production method therefor, and composite, color conversion structure, and electronic device comprising the same
Patent Information
- Application Number
- JP2024133241
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-08
- Filing Date
- 2024-08-08
- Publication Date
- 2025-02-21
AI Technical Summary
【0036】 本発明の半導体ナノ粒子によれば、向上した光学物性(例えば、向上した青色光吸収率及び狭い半値幅、増加した発光効率、抑制されたトラップ発光)のみならず、安定性(例えば、化学的及び/又は熱的安定性)を示すため、電子素子の安定性向上に寄与することができる。また、半導体ナノ粒子を含む色変換パネルは、多様な光源を活用することができ、液晶表示素子、QD OLED素子、及び青色micro LEDにQD色変換層又はピクセルを適用するQD micro LED表示素子で有用に活用することができる。更に、半導体ナノ粒子を含む色変換層は、TV、モニター、モバイル機器、VR/AR、車両用電装ディスプレイなどの各種素子に適用される。
Smart Images

Figure 2025026432000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to semiconductor nanoparticles and a method for producing the same, as well as a composite, a color conversion structure, and an electronic device each containing the same. [Background technology]
[0002] Semiconductor nanoparticles exhibit physical properties (e.g., energy band gap, melting point, etc.) that are known as the intrinsic properties of a material, which differ from bulk materials. Semiconductor nanoparticles are configured to emit light upon energy excitation (e.g., light irradiation or voltage application). Such luminescent nanoparticles may find application in a variety of devices (e.g., electronic devices). From an environmental perspective, it is desirable to develop luminescent nanoparticles that can achieve improved luminescent properties and that do not contain harmful heavy metals such as cadmium. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] US Patent Application Publication No. 2017 / 0052444 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made in consideration of the above-mentioned conventional technology, and an object of the present invention is to provide semiconductor nanoparticles exhibiting improved optical properties and improved stability, a method for producing the same, and a composite, a color conversion structure, and an electronic device containing the same. [Means for solving the problem]
[0005] In order to achieve the above object, one aspect of the present invention provides semiconductor nanoparticles that contain silver, indium, gallium, zinc, and sulfur and emit green light, and the relative molar ratio of zinc in the semiconductor nanoparticles defined by the following formula 1 is 0.25 or more and 0.9 or less. [Formula 1] Relative mole ratio of zinc = [Zn] / ([Ag]+[In]+[Ga]+[Zn])…Equation 1 (In the above formula 1, [Ag], [In], [Ga], and [Zn] are the molar contents of silver, indium, gallium, and zinc, respectively, and the molar ratio of gallium to indium (Ga / In) is greater than 2.5 and less than 5.6 or 5 or less.)
[0006] The charge balance value of the semiconductor nanoparticles defined by the following Equation 2 may be 0.8 or more, 0.9 or more, or 0.93 or more, and 1.4 or less, 1.35 or less, or 1.1 or less. [Formula 2] Charge balance value = {[Ag] + 3 × ([In] + [Ga]) + 2 × [Zn]} / (2 × [S])…Equation 2 (In the above formula 2, [Ag], [In], [Ga], [Zn], and [S] are the molar contents of silver, indium, gallium, zinc, and sulfur, respectively.)
[0007] The relative molar ratio of zinc in the semiconductor nanoparticles may be 0.28 or more, or 0.35 or more, and 0.48 or less, 0.43 or less, 0.33 or less, or 0.31 or less, or greater than 0.48 or 0.6 or more, and 0.75 or less, or 0.67 or less.
[0008] The semiconductor nanoparticles may have a molar ratio of gallium to indium (Ga / In) of 2.9 or more, or 3.5 or more, and 5 or less, 4.5 or less, 4 or less, or 3.9 or less.
[0009] In the semiconductor nanoparticles, the molar ratio of gallium to the sum of indium and gallium [Ga / (In+Ga)] may be greater than 0.72 or 0.73 or more, and may be 0.84 or less, or 0.8 or less.
[0010] The molar ratio of zinc to indium (Zn / In) in the semiconductor nanoparticles may be 2.7 or more and 10.5 or less, or 5.9 or less.
[0011] The semiconductor nanoparticles may have a molar ratio of sulfur to indium (S / In) of 7.5 or more, or 9 or more, and 17 or less, or 12 or less. In the semiconductor nanoparticles, the molar ratio of silver to indium (Ag / In) may be 1.1 or more, or 2.1 or more, and 5 or less, or 3.1 or less.
[0012] In the semiconductor nanoparticles, the molar ratio of gallium to silver (Ga / Ag) may be 1.1 or more, or 1.4 or more, and 3 or less, or 2.8 or less. In the semiconductor nanoparticles, the molar ratio of gallium to the sum of gallium, indium, and silver (Ga / (Ga+In+Ag)) can be 0.45 or more, or 0.48 or more, and 0.7 or less, or 0.6 or less. In the semiconductor nanoparticles, a molar ratio of zinc to sulfur (Zn / S) may be 0.1 or more and 0.8 or less. In the semiconductor nanoparticles, a molar ratio of the sum of indium and gallium to sulfur ((In+Ga) / S) may be 0.1 or more, or 0.25 or more, and 0.8 or less, or 0.5 or less.
[0013] In the semiconductor nanoparticles, the molar ratio of silver to sulfur (Ag / S) may be 0.1 or more and 0.5 or less, or 0.33 or less. In the semiconductor nanoparticles, the molar ratio of silver to the sum of silver, indium, and gallium (Ag / (Ag+In+Ga)) can be 0.2 or more, or 0.3 or more, and 0.5 or less, or 0.4 or less. In the semiconductor nanoparticles, a molar ratio of sulfur to the sum of silver, indium, and gallium (S / (Ag+In+Ga)) may be 1 or more and 2.5 or less. In the semiconductor nanoparticles, a molar ratio of sulfur to the sum of silver, indium, gallium, and zinc (S / (Ag+In+Ga+Zn)) may be 0.8 or more and 1.3 or less. In the semiconductor nanoparticles, the molar ratio of the sum of indium and gallium to silver ((In+Ga) / Ag) may be 1.4 or more and 3.7 or less.
[0014] The semiconductor nanoparticles can include a first particle comprising silver, indium, gallium, and sulfur, and a semiconductor nanocrystal layer disposed on the first particle comprising zinc and sulfur.
[0015] The first particles can include a first semiconductor nanocrystal and, optionally, a second semiconductor nanocrystal. The first semiconductor nanocrystals can include silver, indium, gallium, and sulfur. The first semiconductor nanocrystals or the first particles may be zinc-free. In the semiconductor nanoparticle, the second semiconductor nanocrystal can be disposed on or surround at least a portion of the first semiconductor nanocrystal. The second semiconductor nanocrystals can include gallium, sulfur, and optionally silver. The semiconductor nanocrystal layer can include third semiconductor nanocrystals comprising zinc and sulfur. The second semiconductor nanocrystal can have a different composition than the first semiconductor nanocrystal and the third semiconductor nanocrystal. The third semiconductor nanocrystals can include zinc sulfide. The third semiconductor nanocrystals can have a different composition than the first semiconductor nanocrystals. The semiconductor nanocrystal layer may be the outermost layer of the semiconductor nanoparticle. In the semiconductor nanoparticle, the second semiconductor nanocrystal can be disposed between the first semiconductor nanocrystal and the semiconductor nanocrystal layer. The semiconductor nanoparticles may have a lower indium content adjacent to the particle surface than the indium content in the central portion (eg, core) of the particle. The nanoparticles may have a greater zinc content adjacent the particle surface than the zinc content in the central portion (eg, core) of the particle. In the nanoparticles, the concentration of zinc may be greater on the outside than on the inside of the particle. The thickness of the semiconductor nanocrystal layer can be 0.1 nm or more, or 0.5 nm or more, and 5 nm or less, 3 nm or less, 1.5 nm or less, 1 nm or less, or 0.8 nm or less. The green light may include band edge emission.
[0016] The emission peak wavelength of the green light may be in the range of 500 nm or more, or 505 nm or more, and 580 nm or less, or 550 nm or less. The (absolute) quantum yield of said semiconductor nanoparticles may be 65% or more, or 70% or more, and 98% or less, or 85% or less.
[0017] The half width of the semiconductor nanoparticles can be 40 nm or less, or 35 nm or less, and 5 nm or more, 10 nm or more, 15 nm or more, or 25 nm or more. The trapped emission percentage of the semiconductor nanoparticles, as determined by the following formula 3, may be 25% or less, 20% or less, 19% or less, 18% or less, or 17% or less. [Formula 3] Trap emission percentage = [trap emission area of emission spectrum / total area of emission spectrum] × 100…Equation 3 (In the above formula 3, the trap emission area is the peak area having a wavelength of the emission peak wavelength + 50 nm or more for a given emission peak.)
[0018] In order to achieve the above object, a method for producing semiconductor nanoparticles according to one embodiment of the present invention includes a step of reacting a zinc precursor with a sulfur precursor in the presence of first particles containing indium, gallium, silver, and sulfur to form a semiconductor nanocrystal layer containing zinc and sulfur on the first particles, wherein the step of reacting the zinc precursor with the sulfur precursor includes a step of adding the first particles and the zinc precursor to a reaction medium containing the sulfur precursor and an organic solvent, and the reaction is carried out at a temperature greater than 180°C and less than 240°C.
[0019] The sulfur precursor may include a thiol compound, an isothiocyanate compound, a thiourea compound, or a combination thereof. The zinc precursor may include a Zn halide.
[0020] The temperature of the reaction may be greater than or equal to 205°C and less than or equal to 220°C. The time for the reaction may be 10 minutes or more and 5 hours or less, or 30 minutes or more and 2 hours or less.
[0021] The organic solvent may include an aliphatic (e.g., alkane, alkene, alkyne) hydrocarbon solvent having 5 to 40 carbon atoms, an aromatic hydrocarbon solvent having 6 to 40 carbon atoms, an amine solvent having 5 to 40 carbon atoms (e.g., an aliphatic amine solvent), or a combination thereof. The organic solvent may comprise a mixture of two or more organic solvents.
[0022] The mixture of organic solvents may be a mixture of a first solvent containing an aliphatic hydrocarbon solvent having 5 to 40 carbon atoms and a second solvent containing an amine solvent having 5 to 40 carbon atoms.
[0023] In the mixture of organic solvents, the mixing ratio of the first solvent to the second solvent may be in the range of 1:0.01 to 1:10, 1:0.03 to 1:9, 1:0.05 to 1:8, 1:0.07 to 1:7, 1:0.1 to 1:6, 1:0.2 to 1:5, 1:0.3 to 1:3, 1:0.5 to 1:2, 1:0.8 to 1:1.3, or a combination thereof.
[0024] In one embodiment, the content of the first solvent in the organic solvent mixture may be in excess of the content of the second solvent.
[0025] In said method, said first particles are obtained by a method comprising the following steps: The method includes the steps of obtaining a first semiconductor nanocrystal comprising silver, indium, gallium, and sulfur; providing a reaction medium comprising a first precursor in a second organic solvent; heating the reaction medium at a first temperature; adding the first semiconductor nanocrystal and a second precursor to the reaction medium to obtain a reaction mixture; and heating the reaction medium at a second temperature and reacting for a first time to form first particles (e.g., comprising the first semiconductor nanocrystal and the second semiconductor nanocrystal), wherein one of the first precursor and the second precursor is a gallium precursor and the other is a sulfur precursor.
[0026] The first temperature may be 120°C or more, for example 180°C or more and 280°C or less, and the second temperature may be 190°C or more and 380°C or less. The reaction medium may further comprise an organic ligand. The charge balance value of the first particle at the first time, obtained by the following Equation 5, may be controlled to be 0.8 or more, or 0.9 or more, and 1.3 or less, or 1.1 or less. [Formula 5] Charge balance value = {[Ag] + 3 × ([In] + [Ga])} / (2 × [S]) … Equation 5 (In the above formula 5, [Ag], [In], [Ga], and [S] are the molar contents of silver, indium, gallium, and sulfur, respectively, in the first particles.)
[0027] The first temperature and the second temperature may be different. The second temperature may be greater than the first temperature.
[0028] The gallium precursor may include a gallium halide, gallium acetylacetonate, or a combination thereof. The second organic solvent can be the same as the first organic solvent. The second organic solvent can be different from the first organic solvent. The second organic solvent may include a substituted or unsubstituted aliphatic hydrocarbon solvent having 5 to 40 carbon atoms, a substituted or unsubstituted aromatic hydrocarbon solvent having 6 to 40 carbon atoms, an amine solvent having 5 to 40 carbon atoms (for example, an aliphatic amine solvent), or a combination thereof. The organic ligand may include a thiol compound.
[0029] The second temperature may be 250° C. or more, 260° C. or more, or 290° C. or more and 330° C. or less, and the first time period may be 10 minutes or more and less than 50 minutes. The second reaction temperature can be less than 290° C. (eg, 200° C. or more and 250° C. or less), and the first time period can be 30 minutes or more and 90 minutes or less (or 70 minutes or less, or 60 minutes or less).
[0030] In one embodiment, the ink composition comprises the semiconductor nanoparticles described above and a liquid vehicle. The semiconductor nanoparticles or populations thereof may be dispersed within the liquid vehicle. The liquid vehicle may comprise liquid monomers, (volatile) organic solvents, or a combination thereof. The ink composition may be substantially free of volatile organic solvents. The ink composition may further contain metal oxide fine particles.
[0031] In one embodiment, the composite comprising semiconductor nanoparticles described above comprises a matrix and the semiconductor nanoparticles dispersed in the matrix. The composite may further include metal oxide fine particles. The composite may be configured to emit green light. The composite may be a patterned film. The composite may further include semiconducting nanoparticles configured to emit a second light different from the green light. When kept in air at room temperature (eg, 25° C.) for 48 hours, the relative luminous efficiency of the complex calculated by the following formula 4 may be more than 50% or 60% or more. [Formula 4] Relative luminescence efficiency (%) = [luminescence efficiency of the complex after 48 hours / initial luminescence efficiency of the complex] × 100…Equation 4
[0032] In one embodiment, a color conversion layer (eg, a color conversion structure or color conversion panel) is provided that includes a color conversion region that includes the semiconductor nanoparticles described above. The color conversion panel includes a color conversion layer including a color conversion region, and partitions that define each region of the color conversion layer according to a selection, the color conversion region including a first region corresponding to a first pixel, and the first region may include the semiconductor nanoparticles or the composite.
[0033] In one embodiment, a display panel or display device includes a light source and a color conversion layer (eg, color conversion structure) disposed over the light source.
[0034] In one embodiment, the display panel includes a light-emitting panel (or light source), the color conversion panel, and optionally a light-transmitting layer located between the light-emitting panel and the color conversion panel. The light emitting panel (or light source) may be configured to provide incident light to the color conversion panel. The incident light may include blue light and optionally green light. The blue light may have a peak wavelength in the range of 440 nm to 460 nm or 450 nm to 455 nm. The light source may include organic light emitting diodes, micro LEDs, mini LEDs, LEDs including nanorods, or combinations thereof.
[0035] In one embodiment, an electronic device (or a display device) includes the color conversion panel or the display panel. Effect of the Invention
[0036] The semiconductor nanoparticles of the present invention exhibit not only improved optical properties (e.g., improved blue light absorptance and narrow half-width, increased luminous efficiency, suppressed trap emission) but also stability (e.g., chemical and / or thermal stability), which can contribute to improving the stability of electronic devices. In addition, the color conversion panel containing the semiconductor nanoparticles can utilize various light sources and can be usefully used in liquid crystal display devices, QD OLED devices, and QD micro LED display devices in which QD color conversion layers or pixels are applied to blue micro LEDs. Furthermore, the color conversion layer containing the semiconductor nanoparticles is applied to various devices such as TVs, monitors, mobile devices, VR / AR, and vehicle electronic displays. [Brief description of the drawings]
[0037] [Figure 1] FIG. 1 is a diagram illustrating a trap emission percentage. [Figure 2a] FIG. 2 is a diagram illustrating a pattern formation process (by photolithography) using an ink composition according to an embodiment. [Figure 2b] 1A to 1C are diagrams illustrating a pattern formation process (by an inkjet method) using an ink composition according to an embodiment. [Figure 3a] 1 is a schematic cross-sectional view showing a color conversion panel according to an embodiment. [Figure 3b] 1 is a cross-sectional view of an electronic device (display device) including a color conversion panel and a light source according to an embodiment. [Figure 4a] 1 is a perspective view illustrating an example of a display panel including a color conversion panel according to an embodiment. [Figure 4b] FIG. 2 is an exploded perspective view showing an example of a display element according to an embodiment. [Figure 4c] FIG. 4b is a cross-sectional view of the display panel of FIG. 4a. [Figure 4d] FIG. 11 is an exploded perspective view showing another example of a display element according to an embodiment. [Figure 5a] FIG. 4b is a plan view showing an example of a pixel arrangement of the display panel of FIG. 4a. [Figure 5b] FIG. 2 is a cross-sectional view showing a first example of a light-emitting element. [Figure 5c] FIG. 4 is a cross-sectional view showing a second example of the light-emitting element. [Figure 5d] FIG. 11 is a cross-sectional view showing a third example of a light-emitting element. [Figure 5e] FIG. 11 is a cross-sectional view showing a fourth example of the light-emitting element. [Figure 6] FIG. 5b is a cross-sectional view corresponding to the display panel of FIG. 5a. [Figure 7a] 1 is a schematic cross-sectional view showing a display element (for example, a liquid crystal display element) according to an embodiment. [Figure 7b] 1 is a schematic cross-sectional view showing an electronic device (eg, an electroluminescent device) according to an embodiment. [Figure 8a] FIG. 2 is a diagram showing the mapping results of transmission electron microscope energy dispersive spectroscopy (TEM-EDX) of the semiconductor nanoparticles of Example 1. [Figure 8b] FIG. 2 is a diagram showing the mapping results of transmission electron microscope energy dispersive spectroscopy (TEM-EDX) of the semiconductor nanoparticles of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, specific examples of the embodiments of the present invention will be described in detail with reference to the drawings.
[0039] However, the embodiment to be realized is not limited to the embodiment disclosed below. Unless otherwise defined, all terms (including technical and scientific terms) used in this specification are used as commonly understood by those having ordinary skill in the art. Furthermore, terms defined in commonly used dictionaries are not interpreted ideally or excessively unless explicitly defined otherwise. Throughout the specification, when a part "includes" a certain component, this means that it may further include other components, not excluding other components, unless otherwise specified to the contrary.
[0040] In the drawings, the thickness of layers and regions are exaggerated for clarity, and the same reference numerals are used throughout the specification to refer to similar parts.
[0041] When a part such as a layer, film, region, or plate is said to be "on" another part, this does not only mean that it is "directly on" the other part, but also includes the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.
[0042] Additionally, the singular forms include the plural forms unless the phrase specifically states otherwise. Thus, a reference to a "semiconductor nanoparticle" may refer to one semiconductor nanoparticle or to a plurality of semiconductor nanoparticles.
[0043] Here, the description "free of cadmium (or other toxic heavy metals)" refers to a concentration of cadmium (or the heavy metal) of 100 ppm (by weight) or less, 50 ppm or less, 10 ppm or less, 1 ppm or less, 0.1 ppm or less, 0.01 ppm or less, or substantially 0. In one embodiment, there is substantially no cadmium (or the heavy metal), or if present, it is present in an amount or impurity level below the detection limit of a given detection means.
[0044] Unless otherwise defined below, "substituted" means that a hydrogen atom in a compound is replaced by an alkyl group having 1 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, an alkynyl group having 2 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms, an alkylaryl group having 7 to 30 carbon atoms, an alkoxy group having 1 to 30 carbon atoms, a heteroalkyl group having 1 to 30 carbon atoms, a heteroalkylaryl group having 3 to 30 carbon atoms, a cycloalkyl group having 3 to 30 carbon atoms, a cycloalkenyl group having 3 to 15 carbon atoms, a cycloalkynyl group having 6 to 30 carbon atoms, a heterocycloalkyl group having 2 to 30 carbon atoms, a halogen (-F, -Cl, -Br, or -I), a hydroxy group (-OH), a nitro group (-NO 2 ), cyano group (-CN), amino group (-NRR', where R and R' are each independently hydrogen or an alkyl group having 1 to 6 carbon atoms), azido group (-N 3), amidino group (-C(=NH)NH 2 ), hydrazino group (-NHNH 2 ), hydrazono group (=N(NH 2 ), aldehyde group (-C(=O)H), carbamoyl group (-C(O)NH 2 ), thiol group (-SH), ester group (-C(=O)OR, where R is an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms), carboxyl group (-COOH) or a salt thereof (-C(=O)OM, where M is an organic or inorganic cation), sulfonic acid group (-SO 3 H) or its salt (-SO 3 M, where M is an organic or inorganic cation), a phosphate group (-PO 3 H 2 ) or its salt (-PO 3 MH or -PO 3 M 2 , where M is an organic or inorganic cation, and combinations thereof.
[0045] In addition, unless otherwise defined below, the term "hetero" means containing 1 to 3 heteroatoms selected from N, O, S, Si, and P.
[0046] Furthermore, the term "aliphatic hydrocarbon group" refers to a linear or branched alkyl group having 1 to 30 carbon atoms, a linear or branched alkenyl group having 1 to 30 carbon atoms, or a linear or branched alkynyl group having 1 to 30 carbon atoms; the term "aromatic organic group" refers to an aryl group having 6 to 30 carbon atoms or a heteroaryl group having 2 to 30 carbon atoms; and in this specification, the term "(meth)acrylate" refers inclusively to acrylate and / or methacrylate.
[0047] As used herein, "Group" refers to a Group of the Periodic Table of the Elements.
[0048] Here, a nanoparticle or nanostructure refers to a structure having at least one region or characteristic dimension with a nanoscale dimension. In one embodiment, the dimension of the nanostructure is less than about 500 nm, less than about 300 nm, less than about 250 nm, less than about 150 nm, less than about 100 nm, less than about 50 nm, or less than about 30 nm. Such structures can have any shape. The nanoparticle or nanostructure can have any shape, including but not limited to nanowires, nanorods, nanotubes, multipod-type shapes having two or more pods, nanodots, etc. The nanoparticle or nanostructure can be, for example, substantially crystalline, substantially monocrystalline, polycrystalline, amorphous, or a combination thereof.
[0049] Here, quantum dots refer to nanocrystalline particles (e.g., semiconductor-based) that exhibit quantum confinement or exciton confinement, and are a type of luminescent (e.g., emitting light upon energy excitation) nanoparticles. Here, quantum dots or semiconductor nanoparticles are not limited in shape unless otherwise specified.
[0050] Here, the term "dispersion" refers to a dispersion in which the dispersed phase is a solid and the continuous medium is a liquid or a solid different from the dispersed phase. Here, the term "dispersion" refers to a colloidal dispersion in which the dispersed phase has dimensions of 1 nm or more, for example 2 nm or more, 3 nm or more, or 4 nm or more, and a few micrometers (um) or less (for example, 2 μm or less, or 1 μm or less, 900 nm or less, 800 nm or less, 700 nm or less, 600 nm or less, or 500 nm or less).
[0051] Here, the dimensions (size, thickness, etc.) may be values for a single entity or may be averages for multiple particles, where average is the median or mean. In one embodiment, average is the mean.
[0052] Here, the peak emission wavelength refers to the wavelength at which the light emission spectrum reaches its maximum value.
[0053] Here, quantum efficiency is easily and reproducibly determined using commercially available equipment (e.g., from Hitachi, Ltd. or Hamamatsu Photonics, Inc.) and, for example, by referring to the manual provided by each equipment manufacturer. Quantum efficiency (or quantum yield) is measured in solution or solid state (in a complex). In one embodiment, quantum efficiency (or quantum yield) is the ratio of photons emitted to photons absorbed by a nanostructure or a collection of nanostructures. In one embodiment, quantum efficiency is measured by any method. For example, there are two types of methods for fluorescence quantum yield or efficiency: absolute method and relative method. In this specification, quantum efficiency measured by the absolute method is referred to as absolute quantum efficiency.
[0054] In the absolute method, the fluorescence of all samples is detected through an integrating sphere to obtain the quantum efficiency. In the relative method, the fluorescence intensity of a standard dye (standard specimen) is compared with that of an unknown sample to calculate the quantum efficiency of the unknown sample. Coumarin 153, Coumarin 545, Rhodamine 101 inner salt, Anthracene and Rhodamine 6G are some of the standard dyes used due to their PL wavelengths, but are not limited to these.
[0055] The half-width and emission peak wavelength (eg, photoluminescence (PL) or electroluminescence (EL) wavelength) are measured from an emission (eg, photoluminescence) spectrum obtained by a spectrophotometer, such as a fluorescence spectrophotometer.
[0056] Here, the "first absorption peak wavelength" refers to the wavelength of the first main peak that appears in the lowest energy region of the UV-Vis absorption spectrum.
[0057] Nanoparticles are included in a variety of electronic devices. The electrical and / or optical properties of nanoparticles vary depending on their physical properties (e.g., composition, size, and / or shape). In one embodiment, the semiconductor nanoparticles are semiconductor nanocrystalline particles. Semiconductor nanoparticles, such as quantum dots, have a large surface area per unit volume and exhibit quantum confinement effects, resulting in physical properties that differ from bulk materials of the same composition. For example, nanoparticles, such as quantum dots, absorb energy (e.g., light) from an excitation source, enter an energy excited state, and emit energy corresponding to their band gap energy.
[0058] Semiconductor nanoparticles are used in various electronic devices, such as color conversion panels (e.g., light-emitting color filters). For example, in a display device including a quantum dot-based color conversion panel or emissive color filter, instead of a white light-emitting backlight unit of a liquid crystal display device, a quantum dot layer, which is a light-emitting material, is disposed in front of the device, and blue light (excitation light) provided from a light source is converted into green light or red light by the quantum dot layer. In such a color conversion panel, the color conversion of the excitation light is performed in a relatively forward part of the device, so that the viewing angle problem of the liquid crystal display can be solved by forward scattering of light, and the light loss problem of an absorptive color filter is also solved. In this specification, a color conversion panel means an electronic device including a color conversion layer. Here, the color conversion layer also includes a structure including a color conversion region (e.g., a color conversion structure).
[0059] In a display device including such a color conversion panel, the physical properties (e.g., optical properties and stability) of the luminescent material can directly affect the display quality of the device. For example, the luminescent material included in the color conversion panel disposed relatively forward of the device is required to have not only luminous efficiency but also an improved level of absorptivity for excitation light. When applied to a patterned single film such as a color filter, a decrease in the absorptivity of the excitation light directly causes blue leakage in the display device and negatively affects the color reproduction rate (e.g., DCI matching rate), and the use of an absorptive color filter to prevent blue leakage results in an additional decrease in luminescent efficiency. The decreased absorptivity of nanoparticles leads to decreased brightness in devices including them.
[0060] Many of the semiconductor nanoparticles that exhibit properties (optical properties and / or stability) that are applicable to devices contain cadmium-based compounds (e.g., cadmium chalcogenides). Cadmium poses serious environmental / health problems and is one of the regulated elements. Therefore, in-depth research has been conducted on nanocrystals based on III-V compounds for cadmium-free environmentally friendly nanoparticles. However, there is a technical need to develop environmentally friendly nanoparticles that exhibit increased absorptance, narrower half-widths, and high levels of luminescence efficiency compared to non-cadmium semiconductor nanoparticles based on III-V compounds (e.g., indium phosphide).
[0061] In this embodiment, the semiconductor nanoparticles are free of cadmium, mercury, lead, or a combination thereof.
[0062] In one embodiment, the semiconductor nanoparticles include silver, indium, gallium, zinc, and sulfur, and the semiconductor nanoparticles are configured to emit a first light (e.g., green light or red light). The first light can be green light. The first light can be red light.
[0063] The relative molar ratio of zinc in the semiconductor nanoparticles defined by the following formula 1 is 0.25 or more and 0.9 or less. [Formula 1] Relative mole ratio of zinc = [Zn] / ([Ag]+[In]+[Ga]+[Zn])…Equation 1
[0064] In the above formula 1, [Ag], [In], [Ga], and [Zn] are the molar contents of silver, indium, gallium, and zinc, respectively.
[0065] In the semiconductor nanoparticles, the molar ratio of gallium to indium (Ga / In) is greater than 2.5 and less than 5.6 or 5 or less.
[0066] The semiconductor nanoparticles of the present embodiment have the structure / composition described herein, and thus can achieve improved optical properties (e.g., narrow half-width, increased quantum yield, and blue light absorptivity) while emitting light of a desired wavelength. The semiconductor nanoparticles of the present embodiment exhibit increased stability (chemical stability and / or thermal stability), and a composite containing the same further maintains its initial luminescence properties at a relatively high level even when left in air for a predetermined period of time (e.g., 48 hours or 72 hours).
[0067] The semiconductor nanoparticles of the present embodiment are utilized as a downward conversion material, for example in a color conversion panel or color conversion sheet, and exhibit increased absorptivity per weight of light emitting particles, so that devices such as panels or sheets including the same can be manufactured at reduced cost and provide improved photoconversion. In this embodiment, the semiconductor nanoparticles reduce or suppress light emission in undesired areas (e.g., trapped light emission).
[0068] The present inventors have confirmed that it is not easy to achieve desired luminescence properties (e.g., increased quantum yield with decreased half-width) in the case of semiconductor nanoparticles containing silver (Ag) as well as a Group 13 metal and a chalcogen element. The present inventors have also confirmed that adjusting the composition of semiconductor nanoparticles based on Group 11-13-16 compounds (e.g., charge balance value and / or molar ratio between components, which will be described later) contributes to improving the optical properties of the particles, but that when the semiconductor nanoparticles have a form such as a composite, the optical properties are rapidly decreased or deteriorated. When such semiconductor nanoparticles are applied to a color conversion layer including pixels (e.g., red pixels or green pixels) configured to emit different colors, a relatively high amount of blue light is incident on a relatively narrow area, which may induce photo-bleaching of the semiconductor nanoparticles or deteriorate the polymer components of the composite. In order to apply the semiconductor nanoparticles to an actual device, a composite dispersed in a matrix (e.g., polymer) is prepared, which includes a process of mixing the semiconductor nanoparticles with an organic material such as a polymer and curing the mixture with heat / light. The present inventors have confirmed that the efficiency of semiconductor nanoparticles decreases during the production process of such a composite, and that the efficiency of the composite decreases significantly when it is left in the air, for example.
[0069] The semiconductor nanoparticles of this embodiment are produced by the methods described herein, exhibit the structures and / or characteristics described herein, and can achieve increased stability and contribute to improved device reliability.
[0070] In the semiconductor nanoparticles, the relative molar ratio of zinc is 0.255 or more, 0.26 or more, 0.265 or more, 0.27 or more, 0.275 or more, 0.28 or more, 0.285 or more, 0.29 or more, 0.295 or more, 0.3 or more, 0.31 or more, 0.32 or more, 0.33 or more, 0.34 or more, 0.35 or more, 0.46 or more, 0.37 or more, 0.38 or more, or 0.39 or more, and 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.55 or less, 0.5 or less, 0.49 or less, 0.485 or less, 0.48 or less, 0.475 or less, 0.47 or less, 0.465 or less, 0.4 0.6 or less, 0.455 or less, 0.45 or less, 0.445 or less, 0.44 or less, 0.435 or less, 0.43 or less, 0.425 or less, 0.42 or less, 0.415 or less, 0.41 or less, 0.405 or less, 0.4 or less, 0.395 or less, 0.39 or less, 0.385 or less, 0.38 or less, 0.375 or less, 0.37 or less, 0.365 or less, 0.36 or less, 0.355 or less, 0.35 or less, 0.345 or less, 0.34 or less, 0.335 or less, 0.33 or less, 0.325 or less, 0.32 or less, 0.315 or less, 0.31 or less, 0.305 or less, or 0.3 or less, or any combination thereof.
[0071] In the semiconductor nanoparticles, the molar ratio of gallium to indium (Ga / In) is in the range of 2.55 or more, 2.6 or more, 2.65 or more, 2.7 or more, 2.75 or more, 2.8 or more, 2.85 or more, 2.9 or more, 2.95 or more, 3 or more, 3.05 or more, 3.1 or more, 3.15 or more, 3.2 or more, 3.25 or more, 3.3 or more, 3.35 or more, 3.4 or more, 3.45 or more, or 3.5 or more, and 5.55 or less, 5.5 or less, 5.3 or less, 5.1 or less, 5 or less, 4.9 or less, 4.7 or less, 4.5 or less, 4.3 or less, 4.2 or less, 4.1 or less, 4 or less, 3.9 or less, 3.8 or less, 3.7 or less, 3.6 or less, or 3.55 or less, or any combination thereof.
[0072] In the semiconductor nanoparticles, the molar ratio of gallium to the sum of indium and gallium [Ga / (In+Ga)] is 0.71 or more, 0.715 or more, 0.72 or more, 0.725 or more, 0.73 or more, 0.735 or more, 0.74 or more, 0.745 or more, 0.75 or more, 0.755 or more, 0.76 or more, 0.765 or more, 0.77 or more, 0.775 or more, 0.78 or more, 0.79 or more, 0.80 or more, 0.81 or more, 0.82 or more, 0.83 or more, 0.84 or more, 0.85 or more, 0.86 or more, 0.87 or more, 0.88 or more, 0.89 or more, 0.90 or more, 0.91 or more, 0.92 or more, 0.93 or more, 0.94 or more, 0.95 or more, 0.96 or more, 0.97 or more, 0.98 or more, 0.99 or more, 0.98 or more, 0.99 or more, 0.99 or more, 0.99 or more, 0.90 or more, 0.91 or more, 0.92 or more, 0.93 or more, 0.94 or more, 0.95 or more, 0.96 or more, 0.97 or more, 0.98 or more, 0.9 ... 0.785 or more, 0.79 or more, or 0.795 or more, and 0.845 or less, 0.84 or less, 0.835 or less, 0.83 or less, 0.825 or less, 0.82 or less, 0.815 or less, 0.81 or less, 0.805 or less, 0.8 or less, 0.795 or less, 0.79 or less, 0.785 or less, 0.78 or less, 0.775 or less, or 0.77 or less, or any combination thereof.
[0073] In the semiconductor nanoparticles, the molar ratio of zinc to indium (Zn / In) is 2.5 or more, 2.55 or more, 2.6 or more, 2.65 or more, 2.7 or more, 2.75 or more, 2.8 or more, 2.85 or more, 2.9 or more, 2.95 or more, 3 or more, 3.05 or more, 3.1 or more, 3.2 or more, 3.3 or more, 3.4 or more, 3.5 or more, 3.6 or more, 3.7 or more, 3.8 or more, 3.9 or more, or 4 or more, and 15 or less, 13 or less, 11 or less, 10.5 or less, 10 or less, 9.5 or less, 9 or less, 8.5 or less, 8 or less, 7.5 or less, 7 or less, 6.5 or less, 6 or less, 5.5 or less, or 5 or less.
[0074] In the semiconductor nanoparticles, the molar ratio of sulfur to indium (S / In) is in the range of 7.5 or more, 7.6 or more, 7.8 or more, 8 or more, 8.5 or more, 9 or more, 9.5 or more, 10 or more, 10.5 or more, or 11 or more, and 17 or less, 16.7 or less, 16 or less, 15.5 or less, 15 or less, 14.5 or less, 14 or less, 13.5 or less, 13 or less, 12.5 or less, 12 or less, 11.5 or less, 11.2 or less, 10.5 or less, or 9.8 or less, or any combination thereof.
[0075] In the semiconductor nanoparticles, the molar ratio of silver to indium (Ag / In) is in the range of 1.1 or more, 1.3 or more, 1.4 or more, 1.5 or more, 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, 2 or more, 2.1 or more, 2.2 or more, 2.3 or more, 2.4 or more, or 2.5 or more, and 5 or less, 4.5 or less, 4 or less, 3.5 or less, 3.3 or less, 3.1 or less, 3 or less, 2.9 or less, 2.8 or less, 2.7 or less, or 2.6 or less, or any combination thereof.
[0076] In the semiconductor nanoparticles, the molar ratio of gallium to silver (Ga / Ag) is 1 or more, 1.1 or more, 1.15 or more, 1.18 or more, 1.2 or more, 1.25 or more, 1.3 or more, 1.33 or more, 1.37 or more, 1.4 or more, 1.43 or more, 1.45 or more, 1.5 or more, 1.55 or more, 1.6 or more, 1.65 or more, 1.7 or more, 1.75 or more, 1.8 or more, 1.85 or more, 1. 0.9 or more, 1.95 or more, 2 or more, 2.1 or more, 2.3 or more, or 2.5 or more, and 3 or less, 2.8 or less, 2.75 or less, 2.5 or less, 2.2 or less, 2 or less, 1.9 or less, 1.8 or less, 1.75 or less, 1.7 or less, 1.65 or less, 1.6 or less, 1.55 or less, 1.5 or less, 1.45 or less, 1.4 or less, or 1.35 or less, or any combination thereof.
[0077] In the semiconductor nanoparticles, the molar ratio of zinc to gallium (Zn / Ga) is in the range of 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.78 or more, 0.8 or more, 0.82 or more, 0.85 or more, 0.9 or more, 0.95 or more, 1 or more, 1.2 or more, 1.4 or more, or 1.45 or more, and 3.5 or less, 3.3 or less, 2.7 or less, 2.6 or less, 2 or less, 1.6 or less, 1.55 or less, 1.45 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1 or less, or 0.94 or less, or any combination thereof.
[0078] In the semiconductor nanoparticles, the molar ratio of gallium to the sum of gallium, indium, and silver (Ga / (Ga+In+Ag)) is 0.3 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.46 or more, 0.47 or more, 0.48 or more, 0.49 or more, 0.5 or more, 0.51 or more, 0.52 or more, 0.53 or more, 0.54 or more, 0.55 or more, or 0.56 or more, and 0.8 or less, 0.7 or less, 0.6 or less, 0.57 or less, 0.54 or less, 0.53 or less, 0.52 or less, 0.51 or less, 0.5 or less, 0.49 or less, or 0.485 or less.
[0079] In the semiconductor nanoparticles, the molar ratio of the sum of indium and gallium to sulfur ((In+Ga) / S) is in the range of 0.1 or more, 0.15 or more, 0.26 or more, 0.28 or more, 0.29 or more, 0.3 or more, 0.33 or more, 0.35 or more, 0.4 or more, 0.41 or more, 0.43 or more, 0.45 or more, 0.47 or more, or 0.5 or more, and 0.8 or less, 0.6 or less, 0.55 or less, 0.52 or less, 0.51 or less, 0.5 or less, 0.48 or less, or 0.46 or less, or any combination thereof.
[0080] In the semiconductor nanoparticles, the molar ratio of silver to sulfur (Ag / S) is in the range of 0.05 or more, 0.07 or more, 0.1 or more, 0.12 or more, 0.15 or more, 0.18 or more, 0.25 or more, or 0.3 or more, and 0.5 or less, 0.35 or less, 0.33 or less, 0.28 or less, 0.26 or less, or 0.26 or less, or any combination thereof.
[0081] In the semiconductor nanoparticles, the molar ratio of zinc to sulfur (Zn / S) is in the range of 0.1 or more, 0.15 or more, 0.21 or more, 0.24 or more, 0.245 or more, 0.25 or more, 0.28 or more, 0.3 or more, or 0.35 or more, and 0.8 or less, 0.75 or less, 0.72 or less, 0.7 or less, 0.67 or less, 0.65 or less, 0.6 or less, 0.55 or less, 0.5 or less, 0.49 or less, 0.48 or less, 0.42 or less, or 0.36 or less, or any combination thereof.
[0082] In the semiconductor nanoparticles, the molar ratio of gallium to sulfur (Ga / S) is in the range of 0.2 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.28 or more, 0.3 or more, 0.32 or more, 0.33 or more, 0.35 or more, 0.38 or more, 0.4 or more, 0.45 or more, or 0.5 or more, and 0.6 or less, 0.55 or less, 0.5 or less, 0.46 or less, 0.43 or less, 0.38 or less, or 0.32 or less, or any combination thereof.
[0083] In the semiconductor nanoparticles, the molar ratio of indium to sulfur (In / S) is in the range of 0.05 or more, 0.06 or more, 0.08 or more, 0.09 or more, 0.1 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, or 0.15 or more, and 0.3 or less, 0.25 or less, 0.18 or less, 0.16 or less, 0.11 or less, 0.07 or less, or 0.03 or less, or any combination thereof.
[0084] In the semiconductor nanoparticles, the molar ratio of silver to the sum of silver, indium, and gallium (Ag / (Ag+In+Ga)) is 0.1 or more, 0.15 or more, 0.2 or more, 0.23 or more, 0.27 or more, 0.28 or more, 0.29 or more, 0.3 or more, 0.32 or more, 0.35 or more, 0.37 or more, or 0.39 or more, and 0.5 or less, 0.4 or less, 0.39 or less, 0.38 or less, 0.37 or less, 0.36 or less, 0.33 or less, 0.32 or less, or 0.28 or less, or any combination thereof.
[0085] In the semiconductor nanoparticles, the molar ratio of sulfur to the sum of silver, indium, and gallium (S / (Ag+In+Ga)) is 1 or more, 1.1 or more, 1.15 or more, 1.2 or more, 1.25 or more, 1.3 or more, 1.35 or more, 1.4 or more, 1.45 or more, 1.47 or more, 1.5 or more, 1.55 or more, 1.6 or more, or 1.7 or more, and 2.8 or less, 2.75 or less, 2.7 or less, 2.6 or less, 2.5 or less, 2.3 or less, 2.1 or less, 2 or less, 1.9 or less, 1.7 or less, 1.55 or less, 1.5 or less, 1.45 or less, 1.35 or less, 1.2 or less, or 1.15 or less, or any combination thereof.
[0086] In the semiconductor nanoparticles, the molar ratio of sulfur to the sum of silver, indium, gallium, and zinc (S / (Ag+In+Ga+Zn)) is 0.75 or more, 0.8 or more, 0.82 or more, 0.84 or more, 0.86 or more, 0.9 or more, 0.95 or more, 1 or more, 1.1 or more, or 1.15 or more, and 1.4 or less, 1.35 or less, 1.3 or less, 1.27 or less, 1.26 or less, 1.25 or less, 1.24 or less, 1.21 or less, 1.2 or less, 1.15 or less, or 1.1 or less, or any combination thereof.
[0087] In the semiconductor nanoparticles, the molar ratio of the sum of indium and gallium to silver ((In+Ga) / Ag) is in the range of 1.3 or more, 1.4 or more, 1.5 or more, 1.55 or more, 1.6 or more, 1.63 or more, 1.7 or more, 1.8 or more, or 2 or more, and 3.7 or less, 2.4 or less, 2.37 or less, 2.3 or less, 2 or less, or 1.9 or less, or any combination thereof.
[0088] In one embodiment, the charge balance value of the semiconductor nanoparticles defined by the following formula 2 is in the range of 0.8 or more, 0.85 or more, 0.9 or more, 0.91 or more, 0.92 or more, 0.93 or more, 0.95 or more, 0.98 or more, 0.99 or more, 1.02 or more, or 1.06 or more, and 1.4 or less, 1.35 or less, 1.3 or less, 1.25 or less, 1.2 or less, 1.18 or less, 1.17 or less, 1.15 or less, 1.1 or less, 1.05 or less, or 1 or less, or any combination thereof. [Formula 2] Charge balance value = {[Ag] + 3x([In] + [Ga]) + 2[Zn]} / (2x[S])…Equation 2
[0089] In the above formula 2, [Ag], [In], [Ga], [Zn], and [S] are the molar contents of silver, indium, gallium, and sulfur, respectively.
[0090] The semiconductor nanoparticles include a first particle including silver, indium, gallium, and sulfur, and a semiconductor nanocrystal layer including zinc and sulfur disposed on the first particle. The charge balance value of the first particle (e.g., a particle including a first semiconductor nanocrystal and a second semiconductor nanocrystal) is 0.8 to 1.3, 0.9 to 1.2, 1 to 1.1, or a combination thereof.
[0091] The first particle comprises a first semiconductor nanocrystal (or a core comprising the first semiconductor nanocrystal) and optionally a second semiconductor nanocrystal (or a shell comprising the second semiconductor nanocrystal). In the semiconductor nanoparticle, the second semiconductor nanocrystal is disposed on or surrounds at least a portion of the first semiconductor nanocrystal.
[0092] The first semiconductor nanocrystals include silver, indium, gallium, and sulfur. The first semiconductor nanocrystals or first particles are zinc-free. The second semiconductor nanocrystals include gallium, sulfur, and optionally silver. The second semiconductor nanocrystals have a different composition than the first semiconductor nanocrystals and the third semiconductor nanocrystals. The third semiconductor nanocrystals include zinc sulfide. The third semiconductor nanocrystals have a different composition than the first semiconductor nanocrystals.
[0093] In the semiconductor nanoparticles, the concentration of indium varies radially. In the semiconductor nanoparticles, the indium content in the inner portion of the particle is different from the outer portion of the particle. In one embodiment, the indium content in the portion adjacent to the surface (e.g., the outermost layer or shell) is less than the indium content in the inner portion (or core) of the particle. In one embodiment, the zinc content (concentration) in the portion adjacent to the surface (e.g., the outermost layer) is greater than the zinc content (concentration) in the inner portion (or core) of the particle. The core or first semiconductor nanocrystal is zinc free. In the nanoparticles, the zinc content in the portion adjacent to the particle surface is greater than the zinc content in the center portion (e.g., the core) of the particle. In the nanoparticles, the concentration of zinc is greater outside than inside the particle.
[0094] The first semiconductor nanocrystals include silver, a Group 13 metal (e.g., indium, gallium, or a combination thereof), and a chalcogen element (e.g., sulfur and optionally selenium). The first semiconductor nanocrystals include a four-member alloy semiconductor material based on a Group 11-13-16 compound including silver (Ag), indium, gallium, and sulfur. The first semiconductor nanocrystals include silver indium gallium sulfide, e.g., Ag(In x Ga 1-x )S 2 (x is greater than 0 and less than 1). In the first semiconductor nanocrystal, the molar ratio between each component is adjusted so that the final semiconductor nanoparticle exhibits the desired composition and optical properties (eg, peak emission wavelength).
[0095] The second semiconductor nanocrystals include a Group 13 metal (indium, gallium, or a combination thereof) and a chalcogen element (sulfur, and optionally selenium). The second semiconductor nanocrystals further include silver (Ag). The second semiconductor nanocrystals include silver, gallium, sulfur, and zinc. The second semiconductor nanocrystals include a ternary alloy semiconductor material including silver, gallium, and sulfur. The second semiconductor nanocrystals have a different composition than the first semiconductor nanocrystals.
[0096] The second semiconductor nanocrystals include a Group 13-16 compound, a Group 11-13-16 compound, or a combination thereof. The Group 13-16 compound includes gallium sulfide, gallium selenide, indium sulfide, indium selenide, indium gallium sulfide, indium gallium selenide, indium gallium selenide sulfide, or a combination thereof.
[0097] The band gap energy of the second semiconductor nanocrystal is different from that of the first semiconductor nanocrystal. The second semiconductor nanocrystal covers at least a portion of the first semiconductor nanocrystal. The band gap energy of the second semiconductor nanocrystal is larger or smaller than the band gap energy of the first semiconductor nanocrystal. In the second semiconductor nanocrystal, the molar ratio between each component is adjusted so that the final semiconductor nanoparticle exhibits the desired composition and optical properties.
[0098] The semiconductor nanocrystal layer includes a third semiconductor nanocrystal including zinc and sulfur. The semiconductor nanocrystal layer surrounds the first particle. In the semiconductor nanoparticle, the second semiconductor nanocrystal is disposed between the first semiconductor nanocrystal and the semiconductor nanocrystal layer. The semiconductor nanocrystal layer is the outermost layer of the semiconductor nanoparticle.
[0099] The size or average size (hereinafter referred to as size) of the first semiconductor nanocrystal is 0.5 nm or more, 1 nm or more, 1.5 nm or more, 1.7 nm or more, 1.9 nm or more, 2 nm or more, 2.1 nm or more, 2.3 nm or more, 2.5 nm or more, 2.7 nm or more, 2.9 nm or more, 3 nm or more, 3.1 nm or more, 3.3 nm or more, 3.5 nm or more, 3.7 nm or more, or 3.9 nm or more, and 5 nm or less, 4.5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2 nm or less, or 1.5 nm or less.
[0100] The thickness (eg, average thickness) of the second semiconductor nanocrystals is 0.1 nm or more, 0.3 nm or more, 0.5 nm or more, 0.7 nm or more, or 0.9 nm or more, and 1.5 nm or less, 1 nm or less, or 0.8 nm or less.
[0101] The thickness of the semiconductor nanocrystal layer is 0.1 nm or more, 0.3 nm or more, 0.4 nm or more, 0.5 nm or more, 0.8 nm or more, 1.1 nm or more, 1.3 nm or more, or 1.6 nm or more, and 3 nm or less, 1.5 nm or less, 1 nm or less, or 0.8 nm or less. Alternatively, the thickness of the semiconductor nanocrystal layer is in the range of 0.1 nm to 5 nm, 0.3 nm to 4 nm, 0.5 nm to 3.5 nm, 0.7 nm to 3 nm, 0.9 nm to 2.5 nm, 1 nm to 2 nm, 1.5 nm to 1.7 nm, or a combination thereof.
[0102] In one embodiment, the semiconductor nanoparticles may or may not include lithium. The semiconductor nanoparticles may or may not include an alkali metal, such as sodium or potassium.
[0103] In one embodiment, the size (or average particle size, hereinafter simply referred to as "size") of the semiconductor nanoparticles is 1 nm or more, 1.5 nm or more, 2 nm or more, 2.5 nm or more, 3 nm or more, 3.5 nm or more, 4 nm or more, 4.5 nm or more, 5 nm or more, 5.5 nm or more, 6 nm or more, 6.5 nm or more, 7 nm or more, 7.5 nm or more, 8 nm or more, 8.5 nm or more, 9 nm or more, 9.5 nm or more, 10 nm or more, or 10.5 nm or more, and 50 nm or less, 48 nm or less, 46 nm or less, 44 nm or less, 42 nm or less, 40 nm or less, 35 nm or less, 30 nm or less, 25 nm or less, 20 nm or less, 18 nm or less, 16 nm or less, 14 nm or less, 12 nm or less, 11 nm or less, 10 nm or less, 8 nm or less, 6 nm or less, 5.5 nm or less, or 4 nm or less.
[0104] In this specification, the size of the semiconductor nanoparticles is the particle diameter. The size of the semiconductor nanoparticles is the equivalent diameter obtained by calculation involving converting the two-dimensional area confirmed by electron microscope (e.g., transmission electron microscope) analysis into a circle. The particle size is a value (e.g., nominal particle size) calculated from the composition and emission peak wavelength of the semiconductor nanoparticles.
[0105] The emission peak wavelength of the semiconductor nanoparticles or green light is 500 nm or more, 505 nm or more, 510 nm or more, 515 nm or more, 520 nm or more, 525 nm or more, 530 nm or more, 535 nm or more, 540 nm or more, or 545 nm or more, and 580 nm or less, 575 nm or less, 570 nm or less, 565 nm or less, 560 nm or less, 555 nm or less, 550 nm or less, 545 nm or less, 540 nm or less, 535 nm or less, 530 nm or less, 525 nm or less, 520 nm or less, or 515 nm or less.
[0106] The emission peak wavelength of the semiconductor nanoparticles or red light is in the range of 600 nm to 660 nm, 605 nm to 650 nm, 610 nm to 645 nm, 615 nm to 640 nm, 620 nm to 635 nm, 623 nm to 632 nm, 625 nm to 630 nm, 628 nm to 629 nm, or a combination thereof.
[0107] The semiconductor nanoparticles exhibit a quantum yield of 50% or more. The quantum yield is the absolute quantum yield. The quantum yield is 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, or 95% or more, and 100% or less, 99.5% or less, 99% or less, 98% or less, or 97% or less.
[0108] The semiconductor nanoparticles or the first light (e.g., green light or red light) have a half width of 5 nm or more, 10 nm or more, 15 nm or more, 20 nm or more, 25 nm or more, or 30 nm or more, and 90 nm or less, 85 nm or less, 80 nm or less, 75 nm or less, 70 nm or less, 65 nm or less, 60 nm or less, 55 nm or less, 50 nm or less, 45 nm or less, 40 nm or less, 38 nm or less, 36 nm or less, 35 nm or less, 34 nm or less, 33 nm or less, 32 nm or less, 31 nm or less, 30 nm or less, 29 nm or less, 28 nm or less, 27 nm or less, 26 nm or less, or 25 nm or less.
[0109] In one embodiment, the semiconductor nanocrystal layer contributes to improving the stability of the semiconductor nanoparticles. The first particles based on Group 11-13-16 compounds exhibit relatively improved luminescence efficiency and narrow half-width. However, the inventors have confirmed that the luminescence properties of the first particles decrease rapidly during processes such as the preparation of the composite, and it is difficult to avoid further decrease in luminescence properties even in the composite state when exposed to an external environment (e.g., air, e.g., oxygen or moisture). The semiconductor nanoparticles according to this embodiment exhibit improved process retention in terms of luminescence efficiency during the preparation process of the composite, and the prepared composite exhibits improved stability against the external environment.
[0110] The present inventors have confirmed that forming a zinc chalcogenide-based semiconductor nanocrystal layer on the first particles based on Group 11-13-16 compounds may negatively affect the luminescence properties of the first particles. The present inventors have confirmed that when a semiconductor nanocrystal layer is formed by reacting zinc with a chalcogen element according to the conventional technology, the ratio of trap emission (in other words, emission peak area of the maximum emission peak wavelength + 50 nm or more) in the emission peak of the final particles increases significantly. Without being bound by a particular theory, it is believed that the formation of zinc sulfide-based semiconductor nanocrystals is difficult, or zinc ions are exchanged with gallium in the first particles or diffused inside the first particles, leading to an increase in trap emission in the final semiconductor nanoparticles. The semiconductor nanoparticles of the present embodiment are prepared, for example, by the method described herein, and exhibit increased stability with significantly suppressed trap emission.
[0111] In one embodiment, the first light (e.g., green or red light) comprises band edge emission. In one embodiment, the light emitted by the semiconductor nanoparticles further comprises defect site emission or trap emission. The band edge emission has a smaller offset from the absorption onset energy and is centered at higher energies (lower wavelengths) than the trap emission. The band edge emission has a narrower wavelength distribution than the trap emission. The band edge emission has a normal (e.g., Gaussian) wavelength distribution.
[0112] FIG. 1 is a diagram illustrating the trap emission percentage.
[0113] Referring to FIG. 1 , in the light emission spectrum of the semiconductor nanoparticles, the percentage of the area of the trap emission (T) (e.g., the peak portion of the emission peak that exceeds the emission peak wavelength + 50 nm) to the total area (A) of the emission peak is 25% or less, 24% or less, 23% or less, 22% or less, 21% or less, 20% or less, 15% or less, 12% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, or 2% or less. [Formula 3] Trap emission percentage (%) = [T / A] x 100...Equation 3
[0114] In the above formula 3, T is the trap emission area of the emission spectrum, and A is the total area of the emission spectrum (see FIG. 1).
[0115] The inventors have determined that semiconductor nanoparticles based on Group 13-16 compounds including silver have limitations in suppressing and eliminating trap luminescence. Although providing a zinc chalcogenide layer increases the stability of the semiconductor nanoparticles, the inventors have determined that the formation of the zinc chalcogenide layer increases the trap luminescence of the final particles. The semiconductor nanoparticles of the present embodiment, for example by having the structures / compositions described herein, exhibit an emission spectrum in which trap luminescence is substantially suppressed or eliminated.
[0116] In one embodiment, a method for producing semiconductor nanoparticles includes reacting a zinc precursor with a sulfur precursor in the presence of first particles comprising indium, gallium, silver, and sulfur to form a semiconductor nanocrystal layer comprising zinc and sulfur on the first particles, wherein reacting the zinc precursor with the sulfur precursor includes adding the first particles and the zinc precursor to a reaction medium comprising the sulfur precursor and a first organic solvent, and the reaction is carried out at a temperature greater than 180°C and less than 240°C.
[0117] The details of the semiconductor nanoparticles and the first particles are as described herein.
[0118] The reaction medium is heated to a predetermined temperature (e.g., a temperature below the reaction temperature) in a vacuum atmosphere prior to addition of the first particles and / or zinc precursor, for example, a temperature of 80°C or more, 100°C or more, or 120°C or more, and 200°C or less, 180°C or less, 150°C or less, or 130°C or less.
[0119] The reaction temperature is 203° C. or more, 205° C. or more, 208° C. or more, and 225° C. or less, or 215° C. or less. The reaction time is 10 minutes or more, 30 minutes or more, 40 minutes or more, 1 hour or more, 80 minutes or more, or 90 minutes or more, and 5 hours or less, 4 hours or less, 3 hours or less, 2 hours or less, 90 minutes or less, or 70 minutes or less.
[0120] The first organic solvent includes a substituted or unsubstituted aliphatic (e.g., alkane, alkene, alkyne) hydrocarbon solvent having 5 to 40 carbon atoms, a substituted or unsubstituted aromatic hydrocarbon solvent having 6 to 40 carbon atoms, an amine solvent having 5 to 40 carbon atoms (e.g., an aliphatic amine solvent), a phosphine solvent having 5 to 50 carbon atoms (having a substituted or unsubstituted aliphatic or aromatic group), or a combination thereof. The aliphatic hydrocarbon solvent having 5 to 40 carbon atoms (or having 10 to 20 carbon atoms or 12 to 18 carbon atoms) is octane, heptane, hexane, octadecene, or a combination thereof. The aromatic hydrocarbon solvent having 6 to 40 carbon atoms is toluene, benzene, or the like. The amine solvent having 5 to 40 carbon atoms (or having 10 to 20 carbon atoms or 12 to 18 carbon atoms) includes an aliphatic amine solvent such as trioctylamine, oleylamine, or an aromatic amine solvent such as triphenylamine. Amine solvents include primary amines such as hexylamine, decylamine, stearylamine, etc. The first organic solvent does not include phosphine solvents (having one, two, or three aliphatic or aromatic groups), such as trioctylphosphine.
[0121] The first organic solvent comprises a mixture of two or more organic solvents.
[0122] The mixture of organic solvents is a mixture of a first solvent containing an aliphatic hydrocarbon solvent having 5 to 40 carbon atoms and a second solvent containing an amine solvent having 5 to 40 carbon atoms.
[0123] In the mixture of organic solvents, the mixing ratio of the first solvent to the second solvent is 1:0.01-1:10, 1:0.02-1:9.5, 1:0.03-1:9, 1:0.04-1:8.5, 1:0.05-1:8, 1:0.06-1:7.5, 1:0.07-1:7, 1:0.1-1:6, 1:0.15-1:5.5, 1:0.2-1:5, 1:0.25-1:4.5, 1:0.2 The range is 1:0.5 to 1:4, 1:0.3 to 1:3, 1:0.4 to 1:2.5, 1:0.5 to 1:2, 1:0.7 to 1:1.5, 1:0.75 to 1:1.3, 1:0.78 to 1:1.28, 1:0.8 to 1:1.25, 1:0.85 to 1:0.99, 1:0.88 to 1:0.96, 1:0.9 to 1:0.95, 1:0.93 to 1:0.94, or a combination thereof.
[0124] In one embodiment, the content of the first solvent in the organic solvent mixture is in excess of the content of the second solvent.
[0125] The inventors have surprisingly determined that semiconductor nanoparticles produced by the use of such mixed solvents, for example when provided in the form of a composite, may exhibit even further improved stability (e.g., relative luminescence efficiency when stored in air as described below).
[0126] The manner in which the first particles and / or zinc precursor are added to the (e.g., heated) reaction medium for formation of the zinc chalcogenide can include shot addition (e.g., syringe addition), drop wise, or a combination thereof.
[0127] The inventors have surprisingly determined that when a zinc and sulfur-containing semiconductor nanocrystal layer is formed on a Group 11-13-16-based first particle by the method described herein, the final particle may achieve improved luminescence properties (e.g., narrow half-width, improved QY, and / or suppressed trap emission) as well as stability. Without being bound by any particular theory, it is believed that the method described herein forms a zinc sulfide-containing semiconductor nanocrystal layer without substantial changes to the composition of the first particle (e.g., reduction in gallium content). The inventors have also determined that the zinc-sulfur-containing semiconductor nanocrystal layer thus formed also contributes to improved thermal and atmospheric stability of the final semiconductor nanoparticles.
[0128] In one embodiment, preparing the first particles includes providing a reaction medium including a first precursor in a second organic solvent, heating the reaction medium at a first temperature, adding a first semiconductor nanocrystal and a second precursor to the reaction medium to obtain a reaction mixture, one of the first precursor and the second precursor being a gallium precursor and the other being a sulfur precursor, and heating the reaction medium at a second temperature and reacting for a first period of time to form the first particles. The first temperature is 120° C. or more (e.g., 180° C. or more, 190° C. or more, or 200° C. or more) and 280° C. or less (e.g., 250° C. or less), and the second temperature is 190° C. or more or 240° C. or more, and 380° C. or less or 280° C. or less. The first period of time is controlled such that the first particles achieve a charge balance value as described herein.
[0129] The second organic solvent includes a substituted or unsubstituted aliphatic hydrocarbon solvent having 5 to 40 carbon atoms (e.g., octadecene), a substituted or unsubstituted aromatic hydrocarbon solvent having 6 to 40 carbon atoms (e.g., toluene), an amine solvent having 5 to 40 carbon atoms (e.g., an aliphatic amine solvent such as trioctylamine or oleylamine), or a combination thereof.
[0130] The second organic solvent includes a mixture of two or more organic solvents (e.g., a mixture of an aliphatic hydrocarbon solvent and an aliphatic amine solvent). The second organic solvent is the same as the first organic solvent. The second organic solvent is different from the first organic solvent.
[0131] The first semiconductor nanocrystal, the second semiconductor nanocrystal, and the charge balance value are as described above. The first temperature and the second temperature are different. The second temperature is higher than the first temperature.
[0132] In one embodiment, the first precursor is a sulfur precursor and the second precursor is a gallium precursor, and the method of this embodiment effectively inhibits oxidation of the gallium precursor.
[0133] In one embodiment, the first particles produced are separated and optionally washed, the separation and washing being carried out by methods described herein.
[0134] The first semiconductor nanocrystals are as described herein. The first semiconductor nanocrystals include silver (Ag), indium, gallium, and sulfur. The method for producing the first semiconductor nanocrystals is not particularly limited and can be appropriately selected. In one embodiment, the first semiconductor nanocrystals are obtained by reacting precursors required depending on the composition, such as a silver precursor, an indium precursor, a gallium precursor, and a sulfur precursor, in a solution containing an organic ligand and an organic solvent at a predetermined reaction temperature (e.g., 180°C to 300°C or 200°C to 280°C), and separating the precursors. For the separation and recovery, refer to the method described later.
[0135] The second temperature is higher than the first temperature. The difference between the first temperature and the second temperature is 10°C or more, 20°C or more, 30°C or more, 40°C or more, 50°C or more, 60°C or more, 70°C or more, 80°C or more, 90°C or more, or 100°C or more, and 200°C or less, 190°C or less, 180°C or less, 170°C or less, 160°C or less, 150°C or less, 140°C or less, 130°C or less, 120°C or less, 110°C or less, 100°C or less, 90°C or less, 80°C or less, 70°C or less, 60°C or less, 50°C or less, 40°C or less, 30°C or less, or 20°C or less.
[0136] The first temperature is 120°C or more, 190°C or more, 200°C or more, 210°C or more, 220°C or more, 230°C or more, 240°C or more, or 250°C or more, and 280°C or less, 275°C or less, 270°C or less, 265°C or less, 260°C or less, 255°C or less, 250°C or less, 240°C or less, 230°C or less, 220°C or less, 210°C or less, 200°C or less, 190°C or less, 180°C or less, 170°C or less, 160°C or less, or 150°C or less.
[0137] The second temperature is 210°C or more, 220°C or more, 230°C or more, 240°C or more, 245°C or more, 250°C or more, 255°C or more, 260°C or more, 265°C or more, 270°C or more, 275°C or more, 280°C or more, 285°C or more, 290°C or more, 295°C or more, 300°C or more, 305°C or more, 310°C or more, 315°C or more, 320°C or more, 330°C or more or higher, 335°C or higher, 340°C or higher, or 345°C or higher, and 380°C or lower, 375°C or lower, 370°C or lower, 365°C or lower, 360°C or lower, 355°C or lower, 350°C or lower, 340°C or lower, 330°C or lower, 320°C or lower, 310°C or lower, 300°C or lower, 290°C or lower, 280°C or lower, 270°C or lower, 260°C or lower, or 250°C or lower.
[0138] The first time period is controlled to obtain a charge balance value of the first particles. Without being bound by theory, the inventors have determined that by controlling the first and second temperatures and the first time period in the above-described reaction, the generation of by-products (e.g., gallium oxide) during the formation of nanoparticles can be effectively suppressed, such that the first particles exhibit the above-described charge balance value (and optionally the molar ratios between the components described herein) and achieve the properties described herein.
[0139] In one embodiment, the first time period ranges from 10 minutes to 3 hours, 20 minutes to 150 minutes, 30 minutes to 100 minutes, or a combination thereof. The first time period is selected taking into consideration the type of precursor, the reaction temperature, the desired composition of the final particles, etc.
[0140] In one embodiment, the second reaction temperature is within a relatively high temperature range (e.g., 280° C. or more, 285° C. to 340° C., or 290° C. to 330° C.), and the first time is 10 minutes or more, 15 minutes or more, 20 minutes or more, or 25 minutes or more, and 2 hours or less, 90 minutes or less, 80 minutes or less, 70 minutes or less, 60 minutes or less, 50 minutes or less, 45 minutes or less, 40 minutes or less, or 35 minutes or less.
[0141] In one embodiment, the second reaction temperature is within a relatively low temperature range (e.g., less than 290° C.) and the first reaction time is 30 minutes or more, 35 minutes or more to 40 minutes or more, 45 minutes or more, 50 minutes or more, 55 minutes or more, 60 minutes or more, 65 minutes or more, 70 minutes or more, 75 minutes or more, or 80 minutes or more.
[0142] The type of silver precursor is not particularly limited and can be appropriately selected. The silver precursor includes silver powder, alkylated silver compounds, silver alkoxides, silver carboxylates, silver acetylacetonates, silver nitrates, silver sulfates, silver halides, silver cyanides, silver hydroxides, silver oxides, silver peroxides, silver carbonates, or combinations thereof. The silver precursor includes silver nitrates, silver acetates, silver acetylacetonates, or combinations thereof.
[0143] The type of indium precursor is not particularly limited and can be appropriately selected. The indium precursor is indium powder, alkylated indium compound, indium alkoxide, indium carboxylate, indium nitrate, indium percolate, indium sulfate, indium acetylacetonate, indium halide, indium cyanide, indium hydroxide, indium oxide, indium peroxide, indium carbonate, or a combination thereof. The indium precursor includes indium carboxylate such as indium oleate and indium myristate, indium acetate, indium hydroxide, indium chloride, indium bromide, indium iodide, or a combination thereof.
[0144] The type of gallium precursor is not particularly limited and can be appropriately selected.The gallium precursor is gallium powder, alkylated gallium compound, gallium alkoxide, gallium carboxylate, gallium nitrate, gallium percolate, gallium sulfate, gallium acetylacetonate, gallium halide, gallium cyanide, gallium hydroxide, gallium oxide, gallium peroxide, gallium carbonate, or a combination thereof.The gallium precursor includes gallium chloride, gallium iodide, gallium bromide, gallium acetate, gallium acetylacetonate, gallium oleate, gallium palmitate, gallium stearate, gallium myristate, gallium hydroxide, or a combination thereof.
[0145] The type of sulfur precursor is not particularly limited and is appropriately selected. The sulfur precursor may be an organic solvent dispersion or reaction product of sulfur (e.g., octadecene sulfide (S-ODE), trioctylphosphine-sulfide (S-TOP), tributylphosphine-sulfide (S-TBP), triphenylphosphine-sulfide (S-TPP), trioctylamine-sulfide (S-TOA)), trimethylsilyl alkyl sulfide, trimethylsilyl sulfide, mercaptopropylsilane, ammonium sulfide, sodium sulfide, C1-30 thiol compounds (e.g., alpha-toluenethiol, octanethiol, dodecanethiol, octadecenethiol, etc.), isothiocyanate compounds (e.g., cyclohexyl isothiocyanate), alkylene trithiocarbonate (e.g., ethylene trithiocarbonate), allyl mercaptan (allyl mercaptan), a thiourea compound (e.g., dialkylthiourea having an alkyl group having 1 to 40 carbon atoms, such as dimethylthiourea, diethylthiourea, ethylmethylthiourea, and dipropylthiourea), a thioacetamide, or a combination thereof. The sulfur precursor includes a thiol compound, an isothiocyanate compound, a thiourea compound, or a combination thereof.
[0146] In one embodiment, when forming a semiconductor nanocrystal layer comprising zinc and sulfur, the sulfur precursor includes, but is not limited to, a thiol compound, an isothiocyanate compound, a thiourea compound, or a combination thereof.
[0147] When present, the selenium precursor comprises selenium-trioctylphosphine (Se-TOP), selenium-tributylphosphine (Se-TBP), selenium-triphenylphosphine (Se-TPP), or combinations thereof.
[0148] The type of zinc precursor is not particularly limited and can be appropriately selected. For example, the zinc precursor includes Zn metal powder, alkylated Zn compound, Zn alkoxide, Zn carboxylate, Zn nitrate, Zn percolate, Zn sulfate, Zn acetylacetonate, Zn halide, Zn cyanide, Zn hydroxide, Zn oxide, Zn peroxide, or a combination thereof. The zinc precursor can be dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, etc. In one embodiment, when forming a semiconductor nanocrystal layer containing zinc and sulfur, the zinc precursor can include, but is not limited to, Zn halide.
[0149] The organic ligands are RCOOH and RNH. 2 , R 2 N.H., R. 3 N, R.S.H., R.H. 2 P.O., R. 2 H.P.O., R. 3 P.O., R.H. 2 P, R 2 H.P., R. 3 P, ROH, RCOOR', RPO(OH) 2 , R.H.P.O.H., R. 2POOH (wherein R and R' each independently comprise a substituted or unsubstituted aliphatic hydrocarbon having 1 to 40 carbon atoms (or 3 to 24 carbon atoms) (e.g., an alkyl group, an alkenyl group, an alkynyl group), or a substituted or unsubstituted aromatic hydrocarbon having 6 to 40 carbon atoms (or 6 to 24 carbon atoms) (e.g., an aryl group having 6 to 20 carbon atoms)), or a combination thereof. The organic ligand is bound to the surface of the produced nanoparticles.The organic ligands include methanethiol, ethanethiol, propanethiol, butanethiol, pentanethiol, hexanethiol, heptanethiol, octanethiol, nonanethiol, decanethiol, dodecanethiol, hexadecanethiol, octadecanethiol, benzylthiol; methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, dodecylamine, hexadecylamine, octadecylamine, dimethylamine, diethylamine, dipropylamine; methanoic acid, ethanoic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, dodecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, benzoic acid; substituted or unsubstituted methylphosphines (e.g., trimethylphosphine, methyldiphenylphosphine, etc.), substituted or unsubstituted ethylphosphines (e.g., triethylphosphine, ethyldiphenylphosphine, etc.), substituted or unsubstituted propylphosphine, substituted or unsubstituted butylphosphine, substituted or unsubstituted pentylphosphine, substituted or unsubstituted octylphosphine (e.g., trioctylphosphine (TOP)); phosphine oxides such as substituted or unsubstituted methylphosphine oxide (e.g., trimethylphosphine oxide, methyldiphenylphosphine oxide), substituted or unsubstituted ethylphosphine oxide (e.g., triethylphosphine oxide, ethyldiphenylphosphine oxide), substituted or unsubstituted propylphosphine oxide, substituted or unsubstituted butylphosphine oxide, substituted or unsubstituted octylphosphine oxide (e.g., trioctylphosphine oxide (TOPO)); diphenylphosphine, triphenylphosphine compounds, or oxide compounds thereof; phosphonic acids (phosphonic Examples of the phosphinic acid include, but are not limited to, alkyl phosphinic acids having 5 to 20 carbon atoms, such as hexyl phosphinic acid, octyl phosphinic acid, dodecane phosphinic acid, tetradecane phosphinic acid, hexadecane phosphinic acid, and octadecane phosphinic acid, and alkyl phosphonic acids having 5 to 20 carbon atoms.The organic ligands may be used alone or in mixtures of two or more.
[0150] The (first or second) organic solvent is selected from the group consisting of amine solvents (e.g., C1-50 aliphatic amines), nitrogen-containing heterocyclic compounds such as pyridine; aliphatic hydrocarbons having 6 to 40 carbon atoms (e.g., alkanes, alkenes, alkynes, etc.) such as hexadecane, octadecane, octadecene, and squalane; aromatic hydrocarbons having 6 to 30 carbon atoms such as phenyldodecane, phenyltetradecane, and phenylhexadecane; phosphines substituted with an alkyl group having 6 to 22 carbon atoms such as trioctylphosphine; phosphine oxides substituted with an alkyl group having 6 to 22 carbon atoms such as trioctylphosphine oxide; aromatic ethers having 12 to 22 carbon atoms such as phenyl ether and benzyl ether, and combinations thereof. Amine solvents are compounds having one or more (e.g., two or three) C1-50, C2-45, C3-40, C4-35, C5-30, C6-25, C7-20, C8-15, or C6-22 aliphatic hydrocarbon groups (alkyl, alkenyl, or alkynyl groups). In one embodiment, the amine solvent includes a C6-22 primary amine, such as hexadecylamine, oleylamine, etc.; a C6-22 secondary amine, such as dioctylamine, etc.; a C6-22 tertiary amine, such as trioctylamine, etc.; or a combination thereof.
[0151] In the reaction medium, the content of the organic ligand and each precursor is appropriately selected in consideration of the type of solvent, the type of organic ligand and each precursor, the desired particle size and composition, etc. The molar ratio between each precursor is appropriately selected in consideration of the desired molar ratio in the final nanoparticles, the reactivity between each precursor, etc. The method of adding each precursor is not particularly limited. Each precursor is injected in portions once or more, or from two to ten times or less. The addition of each precursor is carried out simultaneously or sequentially. The reaction is carried out in an inert gas atmosphere, in air, or in a vacuum state, but is not limited thereto.
[0152] After the reaction is complete, the nanoparticles are separated (e.g., precipitated) by adding a nonsolvent to the final reaction solution (e.g., to which the organic ligands have been coordinated). The nonsolvent is a polar solvent that is miscible with the solvent used in the reaction but does not disperse the nanocrystals.
[0153] The non-solvent is determined by the solvent used in the reaction and includes, for example, acetone, ethanol, butanol, isopropanol, ethanediol, water, tetrahydrofuran (THF), dimethylsulfoxide (DMSO), diethylether, formaldehyde, acetaldehyde, the solvents listed and solvents having similar solubility parameters, or combinations thereof.
[0154] The separation is performed by centrifugation, precipitation, chromatography, or distillation. The separated nanocrystals are washed by adding a washing solvent as necessary. The washing solvent is not particularly limited, and an organic solvent or a solvent having a solubility parameter similar to that of the ligand is used. The non-solvent or washing solvent includes, but is not limited to, alcohol; alkane solvent such as hexane, heptane, octane; chloroform; aromatic solvent such as toluene, benzene; or a combination thereof.
[0155] The produced semiconductor nanoparticles are dispersed in a dispersion solvent. The produced semiconductor nanoparticles form an organic solvent dispersion. The organic solvent dispersion does not contain water and / or an organic solvent miscible with water. The dispersion solvent is appropriately selected. The dispersion solvent includes the above-mentioned organic solvent. The dispersion solvent includes a substituted or unsubstituted aliphatic hydrocarbon having 1 to 40 carbon atoms, a substituted or unsubstituted aromatic hydrocarbon having 6 to 40 carbon atoms, or a combination thereof.
[0156] The shape of the produced semiconductor nanoparticles is not particularly limited, and may include, but is not limited to, for example, spheres, polyhedrons, pyramidal, multipods, or cubic shapes, nanotubes, nanowires, nanofibers, nanosheets, or combinations thereof.
[0157] The semiconductor nanoparticles thus produced contain the above-mentioned organic ligands and / or organic solvents on their surfaces, which are bound to the surfaces of the semiconductor nanoparticles of this embodiment.
[0158] In one embodiment, the composite comprises a matrix and semiconductor nanoparticles dispersed in the matrix. The composite further comprises metal oxide particulates. The composite is configured to emit green light. The composite is a patterned film. The composite further comprises semiconductor nanoparticles configured to emit a second light different from the green light. The composite is in the form of a sheet. The sheet further comprises (additional) semiconductor nanoparticles configured to emit the second light different from the green light.
[0159] The semiconductor nanoparticles or composites have improved optical properties (e.g., increased luminous efficiency and narrower half-width) along with an increased level of blue light absorptivity (e.g., improved excitation light absorptivity) and emit light (e.g., first light) of a desired wavelength.
[0160] The composite includes semiconductor nanoparticles or populations thereof (e.g., at a predetermined content) and exhibits increased light absorptance. The composite has an incident light absorptance of 70% or more, 73% or more, 75% or more, 77% or more, 80% or more, 83% or more, 85% or more, 87% or more, 90% or more, 93% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more. The composite has an incident light absorptance of 70%-100%, 80%-98%, 95%-99%, 96%-98%, or a combination thereof.
[0161] The incident light absorptance is defined as follows: Incident light absorption rate = [(B-B') / B] x 100 (%) B: The amount of incident light provided to the complex B': Amount of incident light that passed through the complex
[0162] The light conversion efficiency (CE) of the composite is 7% or more, 8% or more, 9% or more, 10% or more, 11% or more, 12% or more, 12.5% or more, 12.9% or more, 13% or more, 14.5% or more, 15% or more, 15.5% or more, 16% or more, 16.5% or more, 16.7% or more, or 16.9% or more. Light conversion efficiency (CE,%) = [A / (B-B')] x 100 (%) A: The amount of first light emitted from the complex B: The amount of incident light provided to the complex B': Amount of incident light that passed through the complex
[0163] The inventors have confirmed that, in the case of luminescent particles containing semiconductor nanocrystals based on Group 11-13-16 compounds, even if a desired level of optical properties is achieved, when the particles are included in a composite for application in an actual device, the properties are significantly reduced. The semiconductor nanoparticles of the present embodiment have the above-mentioned compositional and / or structural characteristics, and thus can provide a composite exhibiting improved optical properties, and can exhibit a high optical property retention rate even in the form of a single film. The semiconductor nanoparticles of the present embodiment exhibit significantly improved stability (e.g., thermal stability and atmospheric stability).
[0164] Therefore, in one embodiment, the composite containing semiconductor nanoparticles has a process retention rate according to the following formula 6 of 30% or more, 45% or more, 60% or more, 65% or more, or 70% or more. [Formula 6] {Photoconversion rate in composite film state / Quantum yield in solution state}×2×100(%)…Equation 6
[0165] The single membrane maintenance rate is in the range of 30 to 99%, 68 to 95%, 70 to 85%, or a combination thereof.
[0166] In one embodiment, when left in air (e.g., room temperature or 25° C.) for 48 hours, the complex has a relative luminescence efficiency (or stability) defined by the following Formula 7 of 55% or more, 60% or more, 65% or more, 68% or more, or 70% or more. [Formula 7] Relative luminous efficiency (%) = [Quantum efficiency after 48 hours of luminescent film / Initial luminous efficiency of luminescent film] × 100 ... Equation 7
[0167] In one embodiment, the composite is made from an ink composition that includes a liquid vehicle and (e.g., a plurality of) the semiconductor nanoparticles of the present embodiments, the semiconductor nanoparticles being dispersed within the liquid vehicle.
[0168] The liquid vehicle comprises a liquid monomer, an organic solvent, or a combination thereof. The ink composition further comprises or is substantially free of a volatile organic solvent. The ink composition further comprises metal oxide nanoparticles (e.g., dispersed within the liquid vehicle). The ink composition further comprises a dispersant (for dispersing the semiconductor nanoparticles and / or metal oxide nanoparticles). The dispersant comprises a carboxylic acid group-containing organic compound (monomer or polymer). The liquid vehicle does not comprise a (e.g., volatile) organic solvent. The ink composition is a solvent-free system.
[0169] The liquid monomer comprises a (photo)polymerizable monomer containing a carbon-carbon double bond. The composition optionally further comprises a (thermal or photo) initiator. The composition is photo- or thermally initiated to polymerize.
[0170] Details regarding the nanoparticles in the composition (or composite) are as described herein. The content of the nanoparticles in the composition (or composite) is appropriately adjusted in consideration of the desired end use (e.g., color filters, etc.). In one embodiment, the content of the nanoparticles in the composition (or composite) is 1 wt% or more, for example, 2 wt% or more, 3 wt% or more, 4 wt% or more, 5 wt% or more, 6 wt% or more, 7 wt% or more, 8 wt% or more, 9 wt% or more, 10 wt% or more, 15 wt% or more, 20 wt% or more, 25 wt% or more, 30 wt% or more, 35 wt% or more, or 40 wt% or more based on the solid content of the composition or composite (hereinafter, the solid content is the solid content of the composition or the solid content of the composite). The content of the nanoparticles is 70 wt% or less, for example, 65 wt% or less, 60 wt% or less, 55 wt% or less, or 50 wt% or less based on the solid content. The weight percentage of a component relative to the total solid content in the composition represents the content of the component in the composite described below.
[0171] The ink composition according to an embodiment is a nanoparticle-containing photoresist composition applicable in a photolithography method. The ink composition according to an embodiment is a composition that provides a pattern by a printing method (e.g., a droplet ejection method such as inkjet printing). The composition according to an embodiment does not include a conjugated (or conductive) polymer (except for a cull binder described below). The composition according to an embodiment includes a conjugated polymer. Here, the conjugated polymer refers to a polymer having a conjugated double bond in the main chain (e.g., polyphenylenevinylene, etc.).
[0172] In a composition according to an embodiment, the dispersant ensures the dispersibility of the nanoparticles. In an embodiment, the dispersant is a binder (or binder polymer). The binder contains carboxylic acid groups (e.g., in a repeat unit). The binder is an insulating polymer. The binder is a carboxylic acid group-containing compound (monomer or polymer).
[0173] In the composition (or composite), the content of the dispersant is, based on the total solid content of the composition (or composite), 0.5% by weight or more, for example, but not limited to, 1% by weight or more, 5% by weight or more, 10% by weight or more, 15% by weight or more, or 20% by weight or more, and the content of the dispersant is, based on the total solid content, 55% by weight or less, 35% by weight or less, 33% by weight or less, or 30% by weight or less.
[0174] In the composition (or liquid vehicle), the liquid monomer or polymerizable (e.g., photopolymerizable) monomer containing a carbon-carbon double bond (hereinafter, referred to as monomer) includes a (e.g., photopolymerizable) (meth)acrylic monomer. The monomer is a precursor for an insulating polymer.
[0175] The content of the monomer is 0.5% by weight or more, for example, 1% by weight or more, 2% by weight or more, 3% by weight or more, 5% by weight or more, or 10% by weight or more, based on the total weight of the composition. The content of the photopolymerizable monomer is 30% by weight or less, for example, 28% by weight or less, 25% by weight or less, 23% by weight or less, 20% by weight or less, 18% by weight or less, 17% by weight or less, 16% by weight or less, or 15% by weight or less, based on the total weight of the composition.
[0176] The (photo)initiator contained in the composition is for (photo)polymerization of the above-mentioned monomer. The initiator is a compound that generates radical species under mild conditions (e.g., by heat or light) to promote radical reactions (e.g., radical polymerization of monomers). The initiator is a thermal initiator or a photoinitiator. The initiator is not particularly limited and is appropriately selected.
[0177] In the composition, the content of the initiator is appropriately adjusted in consideration of the type and content of the polymerizable monomer used. In one embodiment, the content of the initiator is 0.01 wt% or more, for example 1 wt% or more, and 10 wt% or less, 9 wt% or less, 8 wt% or less, 7 wt% or less, 6 wt% or less, or 5 wt% or less based on the total weight of the composition (or the total weight of the solid content), but is not limited thereto.
[0178] The composition (or complex) further comprises a thiol compound (multi- or monofunctional) having at least one terminal thiol group (or a residue derived therefrom, such as a residue produced by the reaction between a thiol and a carbon-carbon double bond, e.g., a sulfide group), a metal oxide particulate, or a combination thereof.
[0179] Metal oxide particles are TiO 2 , SiO 2 , BaTiO 3 , B.A. 2 TiO 4 , ZnO, or a combination thereof. Within the composition (or composite), the metal oxide content is, based on the total solids content, 1 wt% or more, 2 wt% or more, 3 wt% or more, 5 wt% or more, or 10 wt% or more, and 50 wt% or less, 40 wt% or less, 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, 7 wt% or less, 5 wt% or less, or 3 wt% or less.
[0180] The diameter of the metal oxide fine particles is not particularly limited and may be appropriately selected. The diameter of the metal oxide fine particles is 100 nm or more, for example, 150 nm or more or 200 nm or more, and 1000 nm or less or 800 nm or less.
[0181] The multiple thiol compound is a dithiol compound, a trithiol compound, a tetrathiol compound, or a combination thereof. For example, the thiol compound is glycol di-3-mercaptopropionate, glycol dimercaptoacetate, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(2-mercaptoacetate), 1,6-hexanedithiol, 1,3-propanedithiol, 1,2-ethanedithiol, polyethylene glycol dithiol containing 1 to 10 repeating units of ethylene glycol, or a combination thereof.
[0182] The content of the thiol compound (or a residue derived therefrom) is, based on the total solids content, 50% by weight or less, 40% by weight or less, 30% by weight or less, 20% by weight or less, 10% by weight or less, 9% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, or 5% by weight or less, and 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 5% by weight or more, 10% by weight or more, 15% by weight or more, 18% by weight or more, or 20% by weight or more.
[0183] The composition or liquid vehicle includes an organic solvent. The composition or liquid vehicle does not include an organic solvent. If present, the type of solvent that can be used is not particularly limited. The type and amount of the organic solvent are appropriately determined taking into consideration the above-mentioned main components (i.e., nanoparticles, dispersant, polymerizable monomer, initiator, thiol compound if present) and the types and amounts of other additives described below. The composition includes the solvent in the remaining amount excluding the desired solid content (non-volatile content).
[0184] In one embodiment, examples of the organic solvent include ethylene glycols, glycol ethers, glycol ether acetates, propylene glycols, propylene glycol ethers, propylene glycol ether acetates, amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide, ketones such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), and cyclohexanone, petroleums such as toluene, xylene, and solvent naphtha, esters such as ethyl acetate, butyl acetate, and ethyl lactate, ethers such as diethyl ether, dipropyl ether, and dibutyl ether, chloroform, aliphatic hydrocarbons having 1 to 40 carbon atoms (e.g., alkane, alkene, or alkyne), a halogen (e.g., chloro)-substituted aliphatic hydrocarbons having 1 to 40 carbon atoms (e.g., dichloroethane, trichloromethane, or the like), and aromatic hydrocarbons having 6 to 40 carbon atoms (e.g., toluene, xylene, or the like). aromatic hydrocarbons having 6 to 40 carbon atoms substituted with halogens (e.g., chloro).
[0185] In addition to the above-mentioned components, the composition (or composite) may further contain various additives such as a light diffusing agent, a leveling agent, a coupling agent, etc., as necessary. The components (binder, monomer, solvent, additive, thiol compound, cull binder, etc.) contained in the composition of one embodiment are appropriately selected, and the specific contents thereof can be referred to, for example, the contents described in Patent Document 1 (US-2017-0052444-A1).
[0186] The composition according to one embodiment is prepared by mixing the above-mentioned components sequentially or simultaneously, and the order of mixing is not particularly limited.
[0187] The composition provides a color conversion layer (or a patterned film of the composite) by (e.g., radical) polymerization. The color conversion layer (or the patterned film of the composite) is fabricated using a photoresist composition. Such a method includes forming a film of the above-mentioned composition on a substrate (S1), optionally prebaking the film (S2), exposing selected areas of the film to light (e.g., wavelengths of 400 nm or less) (S3), and developing the exposed film with an alkaline developer to obtain a pattern of the quantum dot polymer composite (S4).
[0188] FIG. 2a is a schematic diagram showing a pattern formation process (photolithography method) using an ink composition according to one embodiment.
[0189] Referring to Fig. 2a, the composition is applied to a substrate to a desired thickness by a suitable method such as spin coating, slit coating, etc. to form a film. The formed film is optionally pre-baked (PRB). The pre-baking conditions such as temperature, time, atmosphere, etc. are well known and may be appropriately selected.
[0190] The formed (or optionally pre-baked) film is exposed to light having a predetermined wavelength under a mask having a predetermined pattern, the wavelength and intensity of the light being selected taking into consideration the type and content of the photoinitiator, the type and content of the quantum dots, etc.
[0191] When the exposed film is treated with an alkaline developer (e.g., immersed or sprayed), the unirradiated parts of the film dissolve, and the desired pattern is obtained. If necessary, the obtained pattern is post-baked (POB) at a temperature of, for example, 150°C to 230°C for a predetermined time (e.g., 10 minutes or more, or 20 minutes or more) to improve the crack resistance and solvent resistance of the pattern.
[0192] When the color conversion layer or the patterned film of the nanoparticle composite has a plurality of repeating sections (in other words, color conversion regions), a plurality of compositions containing quantum dots (e.g., red-emitting quantum dots, green quantum dots, or blue quantum dots as selected) having desired light-emitting properties (such as light-emitting peak wavelength) are prepared for the formation of each repeating section, and the above-mentioned pattern formation process is repeated a required number of times (e.g., two or more times, or three or more times) for each composition to obtain a desired pattern of nanoparticle-polymer composite. For example, the nanoparticle-polymer composite is a pattern in which two or more different color sections (e.g., RGB color sections) are repeated. Such a nanoparticle-polymer composite pattern is advantageously used as a light-emitting color filter in a display device.
[0193] Color conversion layers or patterned films of nanoparticle composites are produced using ink compositions configured to form patterns in an inkjet manner.
[0194] FIG. 2b is a diagram illustrating a pattern formation process (by an inkjet method) using an ink composition according to one embodiment.
[0195] Referring to Figure 2b, such a method includes the steps of preparing an ink composition, providing a substrate (e.g., patterned with electrodes and optionally with bank or trench-type partitions, etc., in pixel regions), and depositing the ink composition on the substrate (or pixel regions) to form, for example, a first composite layer or a first quantum dot layer (or a first region). The method includes depositing the ink composition on the substrate (or pixel regions) to form, for example, a second composite layer or a second quantum dot layer (or a second region). The formation of the first composite layer and the formation of the second composite layer may be performed simultaneously or sequentially.
[0196] The deposition of the ink composition is carried out using a suitable liquid crystal ejection device such as an inkjet or nozzle printing system (e.g., having an ink reservoir and one or more printheads). The deposited ink composition undergoes solvent removal and polymerization upon heating to provide a (first or second) composite layer. Such a method can form highly precise nanoparticle-polymer composite films or patterned membranes in a simple manner and in a short time.
[0197] In one embodiment of the composite (e.g., the first composite), the (polymer) matrix comprises the components described above in relation to the composition, the matrix content of the composite being 10% by weight or more, 20% by weight or more, 30% by weight or more, 40% by weight or more, 50% by weight or more, or 60% by weight or more, and 95% by weight or less, 90% by weight or less, 80% by weight or less, 70% by weight or less, 60% by weight or less, or 50% by weight or less, based on the total weight of the composite.
[0198] The (polymer) matrix comprises at least one of a dispersant (e.g., a carboxylic acid group-containing binder polymer), a polymerization product of a polymerizable monomer containing one or more carbon-carbon double bonds (e.g., two or more, three or more, four or more, or five or more), and a polymerization product between a polymerizable monomer and a multi-thiol compound having at least two thiol groups at its terminals (e.g., an insulating polymer). The matrix comprises a linear polymer, a crosslinked polymer, or a combination thereof. The (polymer) matrix does not comprise a conjugated polymer (except for cardo resins). The matrix comprises a conjugated polymer.
[0199] The crosslinked polymer includes thiolene resins, crosslinked poly(meth)acrylates, crosslinked polyurethanes, crosslinked epoxy resins, crosslinked vinyl polymers, crosslinked silicone resins, or combinations thereof. In one embodiment, the crosslinked polymer is the polymerization product of the above-mentioned polymerizable monomers and, optionally, multiple thiol compounds.
[0200] The linear polymer comprises repeat units derived from a carbon-carbon unsaturated bond (e.g., a carbon-carbon double bond). The repeat units comprise a carboxylic acid group. The linear polymer comprises ethylene repeat units.
[0201] The carboxylic acid group-containing repeat unit includes a unit derived from a monomer containing a carboxylic acid group and a carbon-carbon double bond, a unit derived from a monomer having a dianhydride moiety, or a combination thereof.
[0202] The (polymer) matrix comprises a carboxylic acid group-containing compound (eg, a binder, binder polymer, or dispersant) (eg, for dispersing or binding the nanoparticles).
[0203] The first composite (or film or pattern thereof) has a thickness, for example, of 30 μm or less, such as 25 μm or less, 20 μm or less, 15 μm or less, 10 μm or less, 8 μm or less, or 7 μm or less, and a thickness of more than 2 μm, such as 3 μm or more, 3.5 μm or more, 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, or 10 μm or more.
[0204] The above-mentioned nanoparticles, composites (patterns) containing them, or color conversion panels containing them are included in electronic devices, including, but not limited to, display devices, light-emitting diodes (LEDs), organic light-emitting diodes (OLEDs), quantum dot LEDs, sensors, solar cells, imaging sensors, photodetectors, and liquid crystal display devices.
[0205] The quantum dots described above are included in electronic apparatus. Such electronic apparatus include, but are not limited to, mobile terminal devices, monitors, notebook PCs, televisions, electronic displays, cameras, automobiles, etc. The electronic apparatus is a mobile terminal device, monitor, notebook PC, or television that includes a display element (or light-emitting element) that includes the quantum dots. The electronic apparatus is a camera or mobile terminal device that includes an image sensor that includes the quantum dots. The electronic apparatus is a camera or automobile that includes a photodetector that includes the quantum dots.
[0206] One embodiment provides a color conversion layer (e.g., a color conversion structure or color conversion panel) including a color conversion region that includes the semiconductor nanoparticles described above. The color conversion panel includes a color conversion layer including a color conversion region and partitions that optionally define each region of the color conversion layer, the color conversion region including a first region corresponding to a first pixel, the first region including the semiconductor nanoparticles or composite. In one embodiment of the color conversion panel, the composite is in the form of a patterned film. In another embodiment, the composite has the form of a sheet.
[0207] In one embodiment, the color conversion panel includes a color conversion layer (e.g., color conversion structures) including color conversion regions and partitions selectively defining each region of the color conversion layer. The color conversion regions include a first region corresponding to a first pixel. The first region includes a first composite, the first composite including a matrix and semiconductor nanoparticles dispersed within the matrix, configured to emit a first light. In one embodiment, the semiconductor nanoparticles or a population thereof are provided.
[0208] A color conversion layer (eg, color conversion structure) comprises the composite of one embodiment or a patterned film thereof.
[0209] FIG. 3a is a schematic cross-sectional view showing a color conversion panel according to one embodiment.
[0210] Referring to FIG. 3a, the color conversion panel optionally further includes partitions (eg, black matrix (BM), banks, or a combination thereof) that define each area of the color conversion layer (eg, color conversion structures).
[0211] FIG. 3b is a cross-sectional view of an electronic device (display device) including a color conversion panel and a light source according to an embodiment.
[0212] In the electronic device, a color conversion panel including a color conversion layer or a color conversion structure is disposed on an LED on chip (e.g., a micro LED on chip). Referring to FIG. 3b, a circuit (Si Driver IC) for driving a light source is disposed under a light source (e.g., a blue LED) configured to emit incident light (e.g., blue light). The color conversion layer includes a first composite including semiconductor nanoparticles that emit a first light (e.g., green light), a second composite including semiconductor nanoparticles that emit a second light (red light), and a third composite that emits or passes a third light (e.g., incident light or blue light). A partition (e.g., an inorganic material base such as silicon or silicon oxide or an organic material base) is disposed between each composite. The partition includes a trench hole, a via hole, or a combination thereof. A first optical element (e.g., an absorptive color filter) is disposed on the light extraction surface of the color conversion layer. An additional optical element such as a microlens is further disposed on the first optical element.
[0213] The color conversion region includes a first region configured to emit the above-mentioned first light (or green light) (e.g., upon irradiation with incident light). In one embodiment, the first region corresponds to a green pixel. The first region includes a first composite (e.g., a light-emitting composite). The first light has an emission peak wavelength within a wavelength range described below. The first light will be described in more detail when discussing the semiconductor nanoparticles.
[0214] The emission peak wavelength of green light is 500 nm or more, 501 nm or more, 504 nm or more, 505 nm or more, 520 nm or more, and 580 nm or less, 560 nm or less, 550 nm or less, 530 nm or less, 525 nm or less, 520 nm or less, 515 nm or less, or 510 nm or less.
[0215] The color conversion zone further includes a (e.g., one or more) second zones configured to emit (e.g., upon irradiation with excitation light) a second light (e.g., red light) different from the first light. The second zone includes a second composite. The semiconductor nanoparticle composite in the second zone includes semiconductor nanoparticles (e.g., quantum dots) that emit light at a different wavelength (e.g., a different color) than the nanoparticle composite in the first zone.
[0216] The second light is red light having an emission peak wavelength in the range of 600 nm to 650 nm (e.g., 620 nm to 650 nm). The color conversion panel further includes (one or more) third regions that emit or transmit a third light (e.g., blue light) different from the first light and the second light. The incident light includes the third light (e.g., blue light) and optionally green light. The third light includes blue light having an emission peak wavelength in the range of 380 nm or more (e.g., 440 nm or more, 445 nm or more, 450 nm or more, or 455 nm or more) and 480 nm or less (475 nm or less, 470 nm or less, 465 nm or less, or 460 nm or less).
[0217] In one embodiment, the color conversion panel or color conversion layer includes a plurality of first regions, and the composites are arranged in a predetermined pattern shape to be disposed in the first regions of the color conversion panel, respectively. The composites (or these patterns) are manufactured from the (ink) composition by any method, such as photolithography or inkjet. Thus, the present embodiment relates to a composition comprising semiconductor nanoparticles, which will be described in detail herein.
[0218] Fig. 4a is a perspective view showing an example of a display panel including a color conversion panel according to an embodiment, Fig. 4b is an exploded perspective view showing an example of a display device according to an embodiment, Fig. 4c is a cross-sectional view of the display panel of Fig. 4a, and Fig. 4d is an exploded perspective view showing another example of a display device according to an embodiment.
[0219] In one embodiment, the electronic device or display device (e.g., display panel) further comprises a color conversion layer (or color conversion panel) and optionally a light source. The light source is configured to provide incident light to the color conversion layer or color conversion panel. In one embodiment, the display panel comprises a light emitting panel (or light source), the above-mentioned color conversion panel, and a light-transmitting layer located between the light emitting panel and the color conversion panel. The color conversion panel comprises a substrate, and the color conversion layer is disposed on the substrate (see Figures 4a and 4c).
[0220] The light source or light emitting panel (if present) is configured to provide incident light to the color conversion panel or layer, the incident light having an emission peak wavelength in the range of 440 nm or more, such as 450 nm or more, and 580 nm or less, such as 480 nm or less, 470 nm or less, or 460 nm or less.
[0221] In one embodiment, an electronic device (eg, a light-emitting type device) comprises a sheet of the nanoparticle composite.
[0222] Referring to FIG. 4b, the device includes a backlight unit and a liquid crystal panel, and the backlight unit includes a quantum dot polymer composite sheet (QD sheet). Specifically, the backlight unit has a structure in which a reflector, a light guide plate (LGP), a light source (such as a blue LED), a quantum dot polymer composite sheet (QD sheet), and an optical film (such as a prism, a double brightness enhance film (DBEF)) are stacked. The liquid crystal panel is disposed on the backlight unit and has a structure including a liquid crystal and a color filter between two polarizers (Pol). The quantum dot polymer composite sheet (QD sheet) includes quantum dots that absorb light from a light source and emit red light and quantum dots that emit green light. As the blue light provided from the light source passes through the quantum dot polymer composite sheet, it is combined with the red light and green light emitted from the semiconductor nanoparticles and converted into white light. The white light is separated into blue light, green light, and red light by the color filters in the liquid crystal panel and emitted to the outside for each pixel.
[0223] Referring to FIG. 4d, the backlight unit (BLU) is a direct-type BLU without a light guide plate and includes multiple LEDs (e.g., Mini LEDs).
[0224] The color conversion panel includes a substrate, and the color conversion layer is disposed on the substrate. The color conversion layer or color conversion panel includes a patterned film of nanoparticle composites. The patterned film includes repeating sections configured to emit desired light. The second area is a red light emitting area. The first area is a green light emitting area. The third area is an area that emits or transmits blue light. Details regarding the first, second, and third areas are as described above.
[0225] The light emitting panel or light source is an element that emits incident light (e.g., excitation light). The excitation light includes blue light and optionally green light. The light source includes an LED. The light source includes an organic LED (OLED). The light source includes a micro LED. On the front surface (light emitting surface) of the first and second regions, an optical element that blocks (e.g., reflects or absorbs) blue light (and optionally green light), such as a blue light (and optionally green light) blocking layer or a first optical filter described below, is arranged. When the light source includes blue light emitting organic light emitting diodes and green light emitting organic light emitting diodes, a green light rejection filter is further arranged on the third section through which the blue light passes.
[0226] The light-emitting panel or light source includes a plurality of light-emitting units corresponding to the first and second regions, respectively, and the light-emitting units include a first electrode and a second electrode facing each other, and an (organic) electroluminescent layer disposed between the first and second electrodes. The electroluminescent layer includes an organic light-emitting material. For example, each light-emitting unit of the light source includes an electroluminescent element (e.g., an organic light-emitting diode) configured to emit light of a predetermined wavelength (e.g., blue light, green light, or a combination thereof). The structures and materials of the electroluminescent element and the organic light-emitting diode are known and are not particularly limited.
[0227] The display panel and the color conversion panel will be described in more detail below with reference to the drawings.
[0228] 4a and 4c, a display panel or electronic device 1000 according to the present embodiment includes a light-emitting panel 40 or a light source, and a color conversion panel 50. The display panel or electronic device further includes, but is not limited to, a light-transmitting layer 60 located between the light-emitting panel 40 and the color conversion panel 50, a bonding material 70 bonding the light-emitting panel 40 and the color conversion panel 50, or a combination thereof. The light-transmitting layer includes a passivation layer, a filler material, an encapsulation layer, or a combination thereof. The light-transmitting layer material is appropriately selected and is not particularly limited. The light-transmitting layer material includes an inorganic material, an organic material, an organic-inorganic hybrid material, or a combination thereof.
[0229] The light-emitting panel 40 and the color conversion panel 50 face each other with a light-transmitting layer 60 therebetween, and the color conversion panel 50 is disposed in the direction in which light is emitted from the light-emitting panel 40. The bonding material 70 is disposed along the edges of the light-emitting panel 40 and the color conversion panel 50, and is, for example, a sealing material.
[0230] FIG. 5a is a plan view showing an example of a pixel arrangement of the display panel of FIG. 4a.
[0231] Referring to FIG. 5a, a display panel 1000 according to the present embodiment includes a display area 1000D for displaying an image, and a non-display area 1000P located around the display area 1000D and having a binder 400 disposed therein.
[0232] The display area 1000D includes a number of pixels PX arranged along rows (e.g., in the x direction) and / or columns (e.g., in the y direction), and each pixel PX includes a number of sub-pixels (PX 1 , P.X. 2 , P.X. 3 In the drawing, three sub-pixels (PX 1 , P.X. 2 , P.X. 3) constitutes one pixel, but is not limited thereto and may further include additional sub-pixels such as a white sub-pixel, or may further include one or more sub-pixels displaying the same color. The pixels PX may be arranged, for example, in a Bayer matrix, a PenTile matrix, and / or a diamond matrix, but are not limited thereto.
[0233] Each sub-pixel (PX 1 , P.X. 2 , P.X. 3 ) represents three primary colors or a combination of three primary colors, for example red, green, blue, or a combination thereof. 1 displays red, and the second sub-pixel PX 2 displays green, and the third sub-pixel PX 3 displays blue.
[0234] Although the drawings show an example in which all the sub-pixels have the same size, the present invention is not limited thereto, and at least one of the sub-pixels may be larger or smaller than the other sub-pixels. Although the drawings show an example in which all the sub-pixels have the same shape, the present invention is not limited thereto, and at least one of the sub-pixels may have a shape different from the other sub-pixels.
[0235] In one embodiment of a display panel or electronic device, the light-emitting panel includes a substrate and a (e.g., oxide-based) TFT disposed on the substrate, with a light-emitting element disposed on the TFT (e.g., in a tandem structure).
[0236] The light-emitting element includes a light-emitting layer (e.g., a blue light-emitting layer, a green light-emitting layer, or a combination thereof) between opposing first and second electrodes. A charge generating layer is disposed between each of the light-emitting layers. The first electrode and the second electrode are each patterned with a plurality of electrode elements to correspond to pixels. The first electrode is an anode or a cathode. The second electrode is a cathode or an anode.
[0237] The light emitting element may include an organic LED, a nanorod LED, a mini LED, a micro LED, or a combination thereof.
[0238] 5b to 5e are cross-sectional views showing various examples of light emitting devices.
[0239] In one embodiment, the mini LEDs have a size of, but is not limited to, 100 micrometers (μm) or more, 150 μm or more, 200 μm or more, and 1 millimeter or less, 0.5 millimeter or less, 0.15 millimeter or less, or 0.12 millimeter or less. In one embodiment, the micro LEDs have a size of less than 100 micrometers, 50 micrometers or less, or 10 micrometers or less. The size of the micro LEDs can be, but is not limited to, 0.1 μm or more, 0.5 μm or more, 1 μm or more, or 5 μm or more.
[0240] Referring to FIG. 5b, in this embodiment, the light-emitting element 180 includes a first electrode 181 and a second electrode 182 facing each other, an emission layer 183 located between the first electrode 181 and the second electrode 182, and, optionally, auxiliary layers (184, 185) located between the first electrode 181 and the emission layer 183 and between the second electrode 182 and the emission layer 183, respectively.
[0241] The first electrode 181 and the second electrode 182 are disposed to face each other along the thickness direction (e.g., z direction), and one of the first electrode 181 and the second electrode 182 is an anode, and the other is a cathode. The first electrode 181 is a translucent electrode, a semi-translucent electrode, or a reflective electrode, and the second electrode 182 is a translucent electrode or a semi-translucent electrode.
[0242] The transparent or semi-transparent electrode is formed of a conductive oxide, such as indium tin oxide (ITO), indium zinc oxide (IZO), zinc oxide (ZnO), tin oxide (SnO), aluminum tin oxide (AlTO), fluorine-doped tin oxide (FTO), or a thin single-layer or multi-layer metal thin film, including silver (Ag), copper (Cu), aluminum (Al), magnesium (Mg), magnesium-silver (Mg-Ag), magnesium-aluminum (Mg-Al), or a combination thereof. The reflective electrode includes a metal, a metal nitride, or a combination thereof, including, but not limited to, silver (Ag), copper (Cu), aluminum (Al), gold (Au), titanium (Ti), chromium (Cr), nickel (Ni), alloys thereof, nitrides thereof (e.g., TiN), or a combination thereof.
[0243] Light emitting layer 183 emits a first phosphor that emits light having a blue emission spectrum, a second phosphor that emits light having a green emission spectrum, or a combination thereof.
[0244] The maximum emission wavelength of the blue emission spectrum belongs to a wavelength region of not less than about 400 nm and less than 500 nm, and within the above range, belongs to a wavelength region of about 410 nm to 490 nm, about 420 nm to 480 nm, 430 nm to 470 nm, 440 nm to 465 nm, 445 nm to 460 nm, 450 nm to 458 nm, or a combination thereof.
[0245] The maximum emission wavelength of the green emission spectrum belongs to a wavelength region of not less than about 500 nm and less than 590 nm, and within the above range, belongs to a wavelength region of about 510 nm to 580 nm, about 515 nm to 570 nm, 520 nm to 560 nm, 525 nm to 555 nm, 530 nm to 550 nm, 535 nm to 545 nm, or a combination thereof.
[0246] As an example, the light-emitting layer 183 or the light-emitting material contained therein includes a phosphorescent material, a fluorescent material, or a combination thereof. As an example, the light-emitting material includes an organic light-emitting material, and the organic light-emitting material is a low molecular weight compound, a high molecular weight compound, or a combination thereof. The specific types of the phosphorescent material and the fluorescent material are not particularly limited and are appropriately selected from known materials. As an example, the light-emitting material includes an inorganic light-emitting material, and the inorganic light-emitting material is an inorganic semiconductor, a quantum dot, a perovskite, or a combination thereof. The inorganic semiconductor includes a metal nitride, a metal oxide, or a combination thereof.
[0247] The metal nitrides, metal oxides, or combinations thereof include Group III metals such as aluminum, gallium, indium, thallium, and Group IV metals such as silicon, germanium, tin, and combinations thereof. When the light emitter includes an inorganic light emitter, the light emitting element 180 is a quantum dot light emitting diode, a perovskite light emitting diode, or a micro light emitting diode (μLED). Materials that can be used as inorganic light emitters are known.
[0248] In one embodiment, the light-emitting device 180 further includes auxiliary layers (184, 185). The auxiliary layers (184, 185) are disposed between the first electrode 181 and the light-emitting layer 183 and between the second electrode 182 and the light-emitting layer 183, respectively. The auxiliary layers (184, 185) are charge auxiliary layers for controlling charge injection and / or mobility, respectively. The auxiliary layers (184, 185) are each one or more layers, such as a hole injection layer, a hole transport layer, an electron blocking layer, an electron injection layer, an electron transport layer, a hole blocking layer, or a combination thereof. At least one of the auxiliary layers (184, 185) may be omitted. The material for each auxiliary layer is appropriately selected from among materials known for organic electroluminescent devices, etc.
[0249] Each sub-pixel (PX 1 , P.X. 2 , P.X. 3 The light-emitting elements 180 arranged in each sub-pixel (PX 1 , P.X. 2 , P.X. 3The light emitting elements 180 arranged in the sub-pixels (PX 1 , P.X. 2 , P.X. 3 ) emit light, for example, in the blue emission spectrum, the green emission spectrum, or a combination thereof. 1 , P.X. 2 , P.X. 3 ) are separated by pixel defining films (not shown).
[0250] Referring to FIG. 5c, the light-emitting element 180 is a light-emitting element having a tandem structure, and includes a first electrode 181 and a second electrode 182 facing each other, a first light-emitting layer 183a and a second light-emitting layer 183b located between the first electrode 181 and the second electrode 182, a charge generation layer 186 located between the first light-emitting layer 183a and the second light-emitting layer 183b, and auxiliary layers (184, 185) optionally located between the first electrode 181 and the first light-emitting layer 183a and between the second electrode 182 and the second light-emitting layer 183b, respectively.
[0251] The first electrode 181, the second electrode 182, and the auxiliary layers (184, 185) are as described above.
[0252] The first light-emitting layer 183a and the second light-emitting layer 183b emit light of the same or different emission spectrum. In one embodiment, the first light-emitting layer 183a or the second light-emitting layer 183b emits light of a blue emission spectrum or a green emission spectrum. The charge generation layer 186 injects charges into the first light-emitting layer 183a and / or the second light-emitting layer 183b and adjusts the charge balance between the first light-emitting layer 183a and the second light-emitting layer 183b. The charge generation layer 186 includes, for example, an n-type layer and a p-type layer, and includes, for example, an electron transport material and / or a hole transport material including an n-type dopant and / or a p-type dopant. The charge generation layer 186 is one layer or two or more layers.
[0253] Referring to FIG. 5d, a light-emitting element (e.g., having a tandem structure) includes a first electrode 181 and a second electrode 182 facing each other, a first light-emitting layer 183a, a second light-emitting layer 183b, and a third light-emitting layer 183c located between the first electrode 181 and the second electrode 182, a first charge generation layer 186a located between the first light-emitting layer 183a and the second light-emitting layer 183b, a second charge generation layer 186b located between the second light-emitting layer 183b and the third light-emitting layer 183c, and optional auxiliary layers (184, 185) located between the first electrode 181 and the first light-emitting layer 183a and between the second electrode 182 and the third light-emitting layer 183c, respectively.
[0254] The first electrode 181, the second electrode 182, and the auxiliary layers (184, 185) are as described above.
[0255] The first light emitting layer 183a, the second light emitting layer 183b, and the third light emitting layer 183c each emit light of the same or different emission spectrum. The first light emitting layer 183a, the second light emitting layer 183b, and the third light emitting layer 183c emit blue light. In one embodiment, the first light emitting layer 183a and the third light emitting layer 183c emit light of a blue emission spectrum, and the second light emitting layer 183b emits light of a green emission spectrum. In another embodiment, the first light emitting layer 183a and the third light emitting layer 183c emit light of a green emission spectrum, and the second light emitting layer 183b emits light of a blue emission spectrum.
[0256] The first charge generation layer 186a injects charges into the first light emitting layer 183a and / or the second light emitting layer 183b, and adjusts the charge balance between the first light emitting layer 183a and the second light emitting layer 183b. The second charge generation layer 186a injects charges into the second light emitting layer 183b and / or the third light emitting layer 183c, and adjusts the charge balance between the second light emitting layer 183b and the third light emitting layer 183c. Each of the first and second charge generation layers (186a, 186b) is one layer or two or more layers.
[0257] Referring to FIG. 5 e , a light emitting device 180 includes a first electrode 181 , a second electrode 182 , and a light emitting layer 183 including a plurality of nanostructures 187 .
[0258] Either one of the first electrode 181 and the second electrode 182 is an anode, and the other is a cathode. The first electrode 181 and the second electrode 182 are electrodes patterned according to the arrangement direction of a plurality of nanostructures 187, and include, but are not limited to, conductive oxides such as indium tin oxide (ITO), indium zinc oxide (IZO), zinc oxide (ZnO), tin oxide (SnO), aluminum tin oxide (AlTO), and fluorine-doped tin oxide (FTO), or silver (Ag), copper (Cu), aluminum (Al), gold (Au), titanium (Ti), chromium (Cr), nickel (Ni), alloys thereof, nitrides thereof (e.g., TiN), or combinations thereof.
[0259] The light-emitting layer 183 includes a plurality of nanostructures 187, and each sub-pixel (PX 1 , P.X. 2 , P.X. 3 ) includes a plurality of nanostructures 187. The plurality of nanostructures 187 are arranged along one direction, but are not limited thereto. The nanostructures 187 are compound semiconductors that emit light of a predetermined wavelength when a current is applied, and are linear nanostructures such as nanorods or nanoneedles. The diameter or major axis of the nanostructures 187 is, for example, several nanometers to several hundred nanometers, and the aspect ratio of the nanostructures 187 is in the range of more than about 1, about 1.5 or more, about 2.0 or more, about 3.0 or more, about 4.0 or more, about 4.5 or more, about 5.0 or more, more than about 1 and 20 or less, or about 1.5 to 20, about 2.0 to 20, about 3.0 to 20, about 4.0 to 20, about 4.5 to 20, about 5.0 to 20, or a combination thereof.
[0260] Each nanostructure 187 includes a p-type region 187p, an n-type region 187n, and a multiple quantum well region 187i, and emits light from the multiple quantum well region 187i. The nanostructures 187 include, for example, gallium nitride (GaN), indium gallium nitride (InGaN), aluminum gallium nitride (AlGaN), or a combination thereof, and have, for example, a core-shell structure.
[0261] The nanostructures 187 each emit light of the same or different emission spectrum. In one embodiment, the first nanostructure 187a emits light of a blue emission spectrum, for example, light having a maximum emission wavelength in a wavelength range of about 400 nm to less than 500 nm, about 410 nm to 490 nm, or about 420 nm to 480 nm.
[0262] FIG. 6 shows a schematic cross-sectional view of a device (or display panel) according to an embodiment, the cross-sectional view corresponding to that of the display panel of FIG. 3a.
[0263] Referring to FIG. 6, the light source (or light-emitting panel) includes an organic light-emitting diode that emits blue light (and optionally green light). The organic light-emitting diode includes two or more pixel electrodes formed on a substrate, a pixel defining film formed between adjacent pixel electrodes, an organic light-emitting layer formed on each pixel electrode, and a common electrode layer formed on the organic light-emitting layer. A thin film transistor and a substrate are disposed below the organic light-emitting diode. The pixel regions of the OLED are disposed corresponding to first, second, and third regions, which will be described later. Although the color conversion panel and the light-emitting panel are shown in a separated form in FIG. 6, the color conversion panel is stacked directly above the light-emitting panel.
[0264] A laminate structure including a pattern of nanoparticle composites (e.g., a first region including red quantum dots and a second region including green quantum dots) and a substrate is disposed on the light source. Blue light emitted from the light source is incident on the first and second regions, which emit red and green light, respectively. The blue light emitted from the light source passes through the third region. An element (first optical filter or excitation light blocking layer) that selectively blocks excitation light is disposed between the nanoparticle composite layer (R, G) and the substrate. If the excitation light includes blue and green light, a green light blocking filter is added to the third region. The first optical filter or excitation light blocking layer is described in more detail below.
[0265] Such devices can be fabricated by separately fabricating and then combining the color conversion panel and an LED or OLED (e.g., emitting blue light and optionally green light) as described above, or alternatively, by directly forming a pattern of nanoparticle composites on the LED or OLED.
[0266] In one embodiment of the color conversion panel or display device, the substrate is a substrate comprising an insulating material.
[0267] Substrates include glass; various polymers such as polyesters, such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polycarbonates, and polyacrylates; polysiloxanes (e.g., PDMS); Al 2 O 3 , ZnO, or other inorganic materials; or combinations thereof, but are not limited thereto. The thickness of the substrate is appropriately selected in consideration of the substrate material, etc., and is not particularly limited. The substrate may be flexible. The substrate is configured to have a transmittance of 50% or more, 60% or more, 70% or more, 80% or more, or 90% or more for light emitted from the semiconductor nanoparticles.
[0268] A wiring layer including thin film transistors is formed on the substrate. The wiring layer further includes gate lines, storage voltage lines, gate insulating films, data lines, source electrodes, drain electrodes, a semiconductor layer, a passivation film, etc. The detailed structure of the wiring layer varies depending on the embodiment. The gate lines and storage voltage lines are electrically isolated from each other, and the data lines cross the gate lines and storage voltage lines insulated from each other. The gate electrodes, source electrodes, and drain electrodes respectively constitute a control terminal, an input terminal, and an output terminal of the thin film transistors. The drain electrodes are electrically connected to pixel electrodes, which will be described later.
[0269] The pixel electrode functions as an electrode (e.g., an anode) of the display device. The pixel electrode is formed of a transparent conductive material such as indium tin oxide (ITO) or indium zinc oxide (IZO). Alternatively, the pixel electrode is formed of a material having a light-shielding property such as gold (Au), platinum (Pt), nickel (Ni), tungsten (W), chromium (Cr), molybdenum (Mo), iron (Fe), cobalt (Co), copper (Cu), palladium (Pd), or titanium (Ti). The pixel electrode has a two-layer structure in which the above-mentioned transparent conductive material and the above-mentioned material having a light-shielding property are sequentially laminated.
[0270] A pixel defining layer (PDL) is formed between two adjacent pixel electrodes, overlapping the ends of the pixel electrodes to divide the pixel electrodes into pixel units. The pixel defining layer is an insulating layer that electrically isolates two or more pixel electrodes.
[0271] The pixel definition layer covers only a portion of the upper surface of the pixel electrode, and the remaining portion of the pixel electrode that is not covered by the pixel definition layer forms an opening. An organic light-emitting layer, which will be described later, is formed on the area defined as the opening.
[0272] The organic light emitting layer is defined as each pixel region by the pixel electrode and the pixel defining layer. That is, a region in which one organic light emitting unit layer is formed and contacts one pixel electrode separated by the pixel defining layer is defined as one pixel region. In the display device according to the embodiment, the organic light emitting layer is defined as a first pixel region, a second pixel region, and a third pixel region, and each pixel region is spaced apart by a predetermined distance by the pixel defining layer.
[0273] The organic light emitting layer emits a third light in the visible light region or in the UV region. The first to third pixel regions of the organic light emitting layer may all emit the third light. In one embodiment, the third light includes light having high energy in the visible light region, for example, blue light (and green light, if desired). When all the pixel regions of the organic light emitting layer are designed to emit the same light, the pixel regions of the organic light emitting layer are all formed of the same or similar material or exhibit the same or similar physical properties. Therefore, the difficulty of the process of forming the organic light emitting layer can be significantly reduced, and such a display device can be easily applied to a process of enlarging the size / area of the display device. However, the organic light emitting layer according to the present embodiment is not necessarily limited thereto, and the organic light emitting layer may be configured to emit two or more different lights.
[0274] The organic light emitting layer includes an organic light emitting unit layer for each pixel region, and each organic light emitting unit layer further includes auxiliary layers (eg, a hole injection layer, a hole transport layer, an electron transport layer, etc.) in addition to the light emitting layer.
[0275] The common electrode functions as the cathode of the display device. The common electrode is made of a transparent conductive material such as indium tin oxide (ITO), indium zinc oxide (IZO), etc. The common electrode is integrally formed on the organic light-emitting layer.
[0276] A planarization or passivation layer (not shown) is formed on the common electrode, the planarization layer including an insulating material (e.g., transparent) to ensure electrical insulation with the common electrode.
[0277] In one embodiment, the display device further includes a lower substrate, a polarizer disposed under the lower substrate, and a liquid crystal layer disposed between the laminated structure and the lower substrate, the laminated structure being disposed such that the light emitting layer faces the liquid crystal layer. The display device further includes a polarizer between the liquid crystal layer and the light emitting layer. The light source further includes an LED and, optionally, a light guide plate.
[0278] A display device (eg, a liquid crystal display device) according to one non-limiting embodiment will now be described with reference to the drawings.
[0279] FIG. 7a is a schematic cross-sectional view showing a display element (eg, a liquid crystal display element) according to an embodiment.
[0280] Referring to FIG. 7 a , the display device of this embodiment includes a liquid crystal panel 200 , a polarizer 300 disposed below the liquid crystal panel 200 , and a backlight unit disposed below the polarizer 300 .
[0281] The liquid crystal panel 200 includes a lower substrate 210, a laminate structure, and a liquid crystal layer 220 disposed between the laminate structure and the lower substrate 210. The laminate structure includes a transparent substrate 240, a first optical filter layer, and a self-luminous layer 230 including a pattern of a quantum dot polymer composite, and a second optical filter layer.
[0282] The lower substrate 210, also called an array substrate, is a transparent insulating material substrate. The substrate has been described above. A wiring board 211 is provided on the upper surface of the lower substrate 210. The wiring board 211 includes, but is not limited to, a number of gate lines (not shown) and data lines (not shown) that define pixel regions, thin film transistors provided adjacent to intersections between the gate lines and the data lines, and pixel electrodes for each pixel region. The specific contents of such a wiring board are well known and are not particularly limited.
[0283] A liquid crystal layer 220 is provided on the wiring board 211. The liquid crystal layer 220 includes alignment films 221 on the top and bottom of the layer for initial alignment of the liquid crystal material contained therein. Specific details regarding the liquid crystal material and the alignment films (e.g., the liquid crystal material, the alignment film material, the method of forming the liquid crystal layer, the thickness of the liquid crystal layer, etc.) are well known and are not particularly limited.
[0284] A lower polarizer 300 is provided below the lower substrate. The material and structure of the polarizer 300 are well known and are not particularly limited. A backlight unit (e.g., emitting blue light) is provided below the polarizer 300. An upper optical element or polarizer 300 is provided between the liquid crystal layer 220 and the transparent substrate 240, but is not limited thereto. For example, the upper polarizer is disposed between the liquid crystal layer 220 and the self-luminous layer 230. The polarizer is any polarizer used in liquid crystal display devices. The polarizer is, but is not limited to, TAC (triacetyl cellulose) having a thin thickness of 200 μm or less. In another embodiment, the upper optical element is a refractive index adjustment coating without a polarizing function.
[0285] The backlight unit includes a light source 110. The light source emits blue or white light. The light source includes, but is not limited to, a blue LED, a white LED, a white OLED, or a combination thereof.
[0286] The backlight unit further includes a light guide plate 120. In one embodiment, the backlight unit is an edge type. For example, the backlight unit includes a reflector (not shown), a light guide plate (not shown) provided on the reflector to provide a surface light source to the liquid crystal panel 200, and / or one or more optical sheets (not shown), such as a diffusion plate and a prism sheet, located on the light guide plate, but is not limited thereto. The backlight unit does not need to include a light guide plate. In one embodiment, the backlight unit is a direct lighting type. For example, the backlight unit includes a reflector (not shown), a number of fluorescent lamps arranged at regular intervals on the reflector, or an LED driving board on which a number of light emitting diodes are arranged, and a diffusion plate and one or more optical sheets as appropriate thereon. Details of such a backlight unit (for example, details of each component such as light emitting diodes, fluorescent lamps, light guide plate, various optical sheets, and reflector) are well known and are not particularly limited.
[0287] A black matrix 241 is provided on the bottom surface of the transparent substrate 240, which includes an opening and shields gate lines, data lines, thin film transistors, etc. of a wiring board provided on the lower substrate. For example, the black matrix 241 has a lattice shape. A self-emitting layer 230 having a nanoparticle-polymer composite pattern including a first region R emitting a first light (e.g., red light), a second region G emitting a second light (e.g., green light), and a third region B emitting / transmitting, for example, blue light is provided in the opening of the black matrix 241. If desired, the self-emitting layer further includes one or more fourth sections. The fourth section includes quantum dots emitting light of a color (e.g., cyan, magenta, and yellow) different from the light emitted from the first to third sections.
[0288] The self-emitting layer 230 has a patterned section that is repeated corresponding to the pixel regions formed on the lower substrate 210. A transparent common electrode 231 is provided on the self-emitting color filter layer 230.
[0289] The third region B, which transmits / emits blue light, is a transparent color filter that does not change the emission spectrum of the light source. In this case, blue light emitted from the backlight unit is polarized and enters through the polarizer and the liquid crystal layer, and is emitted as is. If necessary, the third region includes quantum dots that emit blue light.
[0290] As described above, if desired, the display device or light emitting element of an embodiment further includes an excitation light blocking layer or a first optical filter layer (hereinafter referred to as a first optical filter layer). The first optical filter layer is disposed between the bottom surface of the first region R and the second region G and a substrate (e.g., the upper transparent substrate 240) or on the upper surface of the substrate. The first optical filter layer is a sheet having an opening in a portion corresponding to a pixel region (third region) that displays blue, and is therefore formed in a portion corresponding to the first and second regions. That is, the first optical filter layer is integrally formed in the remaining portion except for the portion overlapping the third region as shown in Figs. 2a, 2b, 6, and 7a, but is not limited thereto. Two or more first optical filter layers are disposed separately in the first and second regions and in a portion overlapping the third region as selected. If the light source includes a green light emitting element, a green light blocking layer is disposed on the third region.
[0291] The first optical filter layer, for example, blocks light in a part of the wavelength range of the visible light range and transmits light in the remaining wavelength range, for example, blocks blue light (or green light) and transmits light excluding blue light (or green light). The first optical filter layer transmits, for example, green light, red light, and / or yellow light which is a mixture of these. The first optical filter layer transmits blue light and blocks green light, and may be disposed on blue light emitting pixels.
[0292] The first optical filter layer substantially blocks the excitation light and transmits light in a desired wavelength range, the transmittance of the first optical filter layer for light in the desired wavelength range being about 70% or more, 80% or more, 90% or more, or even 100%.
[0293] The first optical filter layer selectively transmitting red light is disposed at a position overlapping the red light emitting section, and the first optical filter layer selectively transmitting green light is disposed at a position overlapping the green light emitting section.
[0294] The first optical filter layer includes at least one of a first filter region that blocks (e.g., absorbs) blue light and red light and selectively transmits light in a predetermined range (e.g., about 500 nm or more, about 510 nm or more, or about 515 nm or more, and about 550 nm or less, about 545 nm or less, about 540 nm or less, about 535 nm or less, about 530 nm or less, about 525 nm or less, or about 520 nm or less), and a second filter region that blocks (e.g., absorbs) blue light and green light and selectively transmits light in a predetermined range (e.g., about 600 nm or more, about 610 nm or more, or about 615 nm or more, and about 650 nm or less, about 645 nm or less, about 640 nm or less, about 635 nm or less, about 630 nm or less, about 625 nm or less, or about 620 nm or less). If the light source emits a mixture of blue and green light, the first optical filter further includes a third filter region that selectively transmits blue light and blocks green light.
[0295] The first filter region is disposed over the green light-emitting section, the second filter region is disposed over the red light-emitting section, and the third filter region is disposed over the blue light-emitting section.
[0296] The first filter region, the second filter region and, optionally, the third filter region are optically isolated. Such a first optical filter layer contributes to improving the color purity of the display device.
[0297] The display device further includes a second optical filter layer (e.g., a red / green light or yellow light recycling layer) disposed between the light-emitting layer and the liquid crystal layer (e.g., between the light-emitting layer and the upper polarizer) and transmitting at least a portion of the third light (excitation light) and reflecting at least a portion of the first light and / or the second light. The first light is red light, the second light is green light, and the third light is blue light. The second optical filter layer transmits only the third light (B) in the blue light wavelength region having a wavelength region of 500 nm or less, and light in the wavelength region exceeding 500 nm, i.e., green light (G), yellow light, red light (R), etc., does not pass through the second optical filter layer but is reflected. The reflected green light and red light pass through the first and second regions and are emitted to the outside of the display device 10.
[0298] The second optical filter layer or the first optical filter layer is formed as a unitary layer having a relatively flat surface.
[0299] The first optical filter layer includes a polymer thin film containing a dye and / or pigment that absorbs light of a wavelength to be blocked. The second optical filter layer and the first optical filter layer include a single layer having a low refractive index, for example, a transparent thin film having a refractive index of 1.4 or less, 1.3 or less, or 1.2 or less. The second optical filter layer or the first optical filter layer having a low refractive index is, for example, a porous silicon oxide, a porous organic material, a porous organic / inorganic composite, or a combination thereof.
[0300] The first optical filter layer or the second optical filter layer includes a plurality of layers having different refractive indices. The two layers having different refractive indices are formed by alternately stacking them. For example, the first / second optical filter layer is formed by alternately stacking a material having a high refractive index and a material having a low refractive index.
[0301] In one embodiment, the electronic device comprises a light emitting device (eg, an electroluminescent device) that includes the nanoparticles described above.
[0302] FIG. 7b is a schematic cross-sectional view illustrating an electronic device (eg, an electroluminescent device) according to an embodiment.
[0303] Referring to FIG. 7b, the light-emitting device includes an anode 1 and a cathode 5 facing each other, a quantum dot light-emitting layer 3 located between the anode and the cathode and including a plurality of quantum dots, and a hole auxiliary layer 2 disposed between the anode and the quantum dot light-emitting layer. The hole auxiliary layer further includes a hole injecting layer (HIL), a hole transporting layer (HTL), an electron blocking layer (EBL), or a combination thereof. The hole auxiliary layer includes any organic / inorganic material having hole properties. The quantum dot light-emitting device further includes an electron auxiliary layer 4 between the cathode and the quantum dot light-emitting layer. The electron auxiliary layer further includes an electron injecting layer (EIL), an electron transporting layer (ETL), a hole blocking layer (HBL), or a combination thereof. The electron auxiliary layer includes any organic / inorganic material having electronic properties.
[0304] Specific examples are presented below. However, the examples described below are merely intended to specifically illustrate or explain the invention, and are not intended to limit the scope of the invention. EXAMPLES
[0305] <Analysis method>
[0306] [1] Photoluminescence analysis Photoluminescence (PL) spectra of the prepared nanoparticles and the complexes containing the same were obtained using a Hitachi F-7100 spectrophotometer at an excitation wavelength of 450 nm.
[0307] [2] ICP analysis Inductively coupled plasma atomic emission spectrometry (ICP-AES) was performed using a Shimadzu ICPS-8100.
[0308] [3] Blue light absorptance and photoconversion efficiency (CE) for the composite The amount of incident light having a wavelength of 450 nm (B) was measured using the integrating hemisphere of an absolute quantum efficiency measurement device (QE-2100, Otsuka). Next, the QD-polymer composite was placed in the integrating hemisphere, and the amount of the first light emitted from the composite by irradiating the composite with incident light (A) and the amount of the incident light that passed through the composite (B') were measured.
[0309] The incident light absorptance was calculated from the measured values using the following formula 8. [Formula 8] Blue light absorption rate (%)=[(B-B') / B]×100(%) Light conversion efficiency (CE,%) = [A / (B-B')] x 100(%) ... Equation 8
[0310] [4] Transmission electron microscope (TEM) analysis and TEM-EDX (energy dispersive spectroscopy) analysis Transmission electron microscopy and EDX analysis of the prepared nanoparticles were carried out using a UT F30 Tecnai electron microscope.
[0311] <Reference Example 1>
[0312] A 0.06M silver precursor-containing solution (hereinafter, abbreviated as "silver precursor") was prepared by dissolving silver acetate in oleylamine. A 1M sulfur precursor-containing solution (hereinafter, abbreviated as "sulfur precursor") was prepared by dispersing sulfur in oleylamine. A 1M indium precursor-containing solution (hereinafter, abbreviated as "indium precursor") was prepared by dissolving indium chloride in ethanol.
[0313] Gallium acetylacetonate, octadecene (ODE), and dodecanethiol were placed in a 100 mL reaction flask and heated under vacuum at 120°C for 10 minutes. The flask was cooled to room temperature and the gas in the flask was replaced with nitrogen, after which a silver precursor, a sulfur precursor, and an indium precursor were placed in the flask and the flask temperature was raised to a reaction temperature (210°C) and reacted for 60 minutes or less. The flask temperature was lowered to 180°C, trioctylphosphine (TOP) was added, and hexane and ethanol were added to the resulting mixture to promote precipitation, and the precipitate (first semiconductor nanocrystals) was separated by centrifugation.
[0314] The molar ratio of indium precursor, gallium precursor, and sulfur precursor used was 1:2.3:4.8.
[0315] Gallium chloride was dissolved in trioctylphosphine to prepare a 1 M gallium precursor-containing solution (hereinafter, gallium precursor).
[0316] Dimethylthiourea (DMTU) and oleylamine were added to the flask and vacuum treated at 120°C for 10 minutes. 2 The inside of the reaction flask was replaced with 1, heated to 240°C, and then the first semiconductor nanocrystal, gallium precursor, and silver compound (silver acetate) were added. After reacting for about 30 minutes, the reactor was heated to 260°C (second temperature) and further reacted for about 40 minutes. The temperature of the reaction solution was made 180°C, trioctylphosphine was added, and the solution was cooled to room temperature, and hexane and ethanol were added to promote precipitation to obtain the first particles, which were then collected by centrifugation and redispersed in toluene. The molar ratio of the gallium precursor and sulfur precursor used was 1:1.3. The content of the silver compound was 3.5 mol% relative to the gallium precursor.
[0317] The obtained semiconductor nanoparticles were subjected to ICP-AES analysis, and the results are shown in Table 1. The obtained semiconductor nanoparticles were subjected to photoluminescence analysis, and the results are shown in Table 2.
[0318] <Example 1>
[0319] Zinc chloride was dissolved in trioctylphosphine (TOP) to prepare a 0.5 M zinc precursor-containing solution (hereinafter, zinc precursor).
[0320] Dimethylthiourea (DMTU) was dissolved in a mixed solvent of oleylamine and octadecene (0.5 M) in a 100 mL flask and vacuum-treated at 120 °C for 10 minutes. 2 The inside of the reaction flask was replaced with 100 ml of hexane, and the flask was heated to 210° C., and the first particles and zinc precursor obtained in Reference Example 1 were added thereto, followed by reaction for 40 minutes. The temperature of the reaction solution was raised to 180° C., trioctylphosphine was added thereto, and the solution was cooled to room temperature. Hexane and ethanol were added to precipitate the generated nanoparticles, and the obtained semiconductor nanoparticles were collected by centrifugation and redispersed in toluene.
[0321] The molar ratio of zinc precursor and sulfur precursor used was 1:1.
[0322] The resulting nanoparticles were subjected to ICP-AES analysis, the results of which are shown in Table 1. The resulting nanoparticles were subjected to optical emission spectroscopy analysis, the results of which are shown in Table 2.
[0323] The resulting nanoparticles were subjected to TEM-EDS mapping analysis, the results of which are shown in Figures 8a and 8b.
[0324] Figure 8a shows the mapping results of transmission electron microscope energy dispersive spectroscopy (TEM-EDX) of the semiconductor nanoparticles of Example 1, and Figure 8b shows the mapping results of transmission electron microscope energy dispersive spectroscopy (TEM-EDX) of the semiconductor nanoparticles of Example 1.
[0325] 8a and 8b, it was confirmed that the obtained particles contained silver, indium, gallium, and zinc, with indium present inside the particles and a higher zinc content in the portion adjacent to the particle surface than inside the particles.
[0326] <Example 2>
[0327] Semiconductor nanoparticles were prepared in the same manner as in Example 1, except that the content of the zinc precursor was increased by approximately two times.
[0328] The obtained semiconductor nanoparticles were subjected to ICP-AES analysis, and the results are shown in Table 1. The obtained semiconductor nanoparticles were subjected to photoluminescence analysis, and the results are shown in Table 2.
[0329] <Example 3>
[0330] Nanoparticles were prepared in the same manner as in Example 1, except that the content of the zinc precursor was increased by approximately 3.5 times.
[0331] The resulting nanoparticles were subjected to ICP-AES analysis, the results of which are shown in Table 1. The resulting nanoparticles were subjected to optical emission analysis, the results of which are shown in Table 2.
[0332] <Comparative Example 1>
[0333] Semiconductor nanoparticles were produced in the same manner as in Example 2, except that the reaction temperature was 150°C.
[0334] The obtained semiconductor nanoparticles were subjected to ICP-AES analysis, and the results are shown in Table 1. The obtained semiconductor nanoparticles were subjected to photoluminescence analysis, and the results are shown in Table 2.
[0335] <Comparative Example 2>
[0336] Semiconductor nanoparticles were prepared in the same manner as in Example 2, except that the reaction temperature was 180°C.
[0337] The obtained semiconductor nanoparticles were subjected to ICP-AES analysis, and the results are shown in Table 1. The obtained semiconductor nanoparticles were subjected to photoluminescence analysis, and the results are shown in Table 2.
[0338] <Comparative Example 3>
[0339] Semiconductor nanoparticles were produced in the same manner as in Example 2, except that the reaction temperature was 240°C.
[0340] The obtained semiconductor nanoparticles were subjected to ICP-AES analysis, and the results are shown in Table 1. The obtained semiconductor nanoparticles were subjected to photoluminescence analysis, and the results are shown in Table 2.
[0341] <Experimental Example 1: Preparation of the Complex and its Luminescence Properties>
[0342] [1] A toluene solution of the semiconductor nanoparticles obtained in Examples 1 to 3 and the semiconductor nanoparticles obtained in Comparative Examples 1 to 3 was mixed with a binder (four-membered copolymer of methacrylic acid, benzyl methacrylate, hydroxyethyl methacrylate, and styrene, acid value: 130 mg KOH / g, molecular weight: 8000) solution (PGMEA concentration: 30 wt%) to produce a nanoparticle binder dispersion.
[0343] A composition was prepared by mixing the nanoparticle binder dispersion with hexaacrylate having the following structure as a photopolymerizable monomer, an oxime ester compound as an initiator, TiO2 and PGMEA as light diffusing agents. [ka]
[0344] The composition produced contains 20% by weight of semiconductor nanoparticles, based on the total solids weight.
[0345] The photosensitive composition was spin-coated on a glass substrate at 600 rpm for 5 seconds to obtain a film. The obtained film was pre-baked (PRB) at 100°C for 2 minutes. The pre-baked film was irradiated with light (wavelength: 395 nm, intensity: 4 J) and heat-treated at 180°C for 30 minutes to obtain a composite (thickness: approximately 7 μm).
[0346] The absorptivity, photoconversion efficiency (CE), and process retention rate of the composite were measured, and the results are summarized in Table 2 below.
[0347] The process retention rate was measured for a portion of the obtained film, and the results are shown in Table 3 below.
[0348] [Table 1]
[0349] In Table 1 above, the relative molar ratio of Zn = Zn / (Ag+In+Ga+Zn) Charge balance value = {[Ag] + 3 × ([In] + [Ga]) + 2 × [Zn]} / (2 × [S])
[0350] where [Ag], [In], [Ga], [Zn], and [S] are the molar contents of silver, indium, gallium, zinc, and sulfur, respectively, in the nanoparticles.
[0351] [Table 2]
[0352] [Table 3]
[0353] The thermal stability of the complex is calculated by the following formula 9. [Formula 9] Thermal stability of the complex (%) = [CE of the complex after POB / CE of the complex after PRB] × 100…Equation 9 As can be seen from the results in Tables 2 and 3 above, the nanoparticles of the Examples exhibit significantly improved luminescence properties and stability compared to the Comparative Examples.
[0354] <Experimental Example 2: Evaluation of film stability in air>
[0355] Composites containing semiconductor nanoparticles of Examples 1, 2, and 3, and Reference Example 1 were produced in the same manner as in Experimental Example 1, and the produced films were left in air at room temperature for 48 hours. The initial luminescence efficiency of the composites and the luminescence efficiency after 48 hours were measured to determine their 48-hour stability (relative luminescence efficiency). The measurement results are summarized in Table 4.
[0356] [Table 4]
[0357] From the results in Table 4, it was confirmed that the semiconductor nanoparticles of Examples 1 to 3 may exhibit significantly improved stability compared to the semiconductor nanoparticles of Reference Example 1, which does not include a ZnS semiconductor nanocrystal layer.
[0358] <Experimental Example 3: Comparison of luminous efficiency excluding trap luminescence>
[0359] The tail emission percentage of more than 50 nm above the emission peak wavelength was measured for the composites containing the semiconductor nanoparticles of Example 1 and Comparative Example 3. As a result, it was confirmed that the tail emission percentage of the composite containing the semiconductor nanoparticles of Comparative Example 3 was 1.3 times higher than the tail emission percentage of the composite containing the semiconductor nanoparticles of Example 1. The results suggest that the proportion of tail emission is very high in the light conversion efficiency (CE, 19%) of the composite containing the semiconductor nanoparticles of Comparative Example 3.
[0360] Although the embodiments of the present invention have been described in detail above with reference to the drawings, the present invention is not limited to the above-described embodiments and can be modified in various ways without departing from the technical spirit of the present invention. [Explanation of symbols]
[0361] 1 Anode 2. Hole auxiliary layer 3. Quantum dot light-emitting layer 4 Electronic auxiliary layer 5 Cathode 40 Light-emitting panel 50 Color Conversion Panel 60 Translucent layer 70 Binding material 100 Electronic elements 110 Light source 120 Light guide plate 180 Light emitting element 181, 182 1st, 2nd electrode 183 Light-emitting layer 183a, 183b, 183c First to third light-emitting layers 184, 185 auxiliary layer 186 Charge generation layer 186a, 186b 1st and 2nd charge generation layer 187 Nanostructures 187i Multiple quantum well region 187n n-type region 187p p-type region 200 LCD Panel 210 Lower Board 211 Wiring board 220 Liquid crystal layer 221 Orientation Film 230 Self-luminous layer 231 Transparent common electrode 240 Transparent Substrate 241 Black Matrix 300 Polarizing Plate 400 Binding material 1000 Display panel (electronic element) 1000D display area 1000P hidden area PX pixels PX 1 ~PX 3 Subpixel
Claims
1. 1. A semiconductor nanoparticle comprising: configured to emit green light comprising silver, indium, gallium, zinc, and sulfur; A semiconductor nanoparticle, characterized in that the relative molar ratio of zinc in the semiconductor nanoparticle, defined by the following formula 1, is 0.25 or more and 0.9 or less. [Formula 1] Relative molar ratio of zinc=[Zn] / ([Ag]+[In]+[Ga]+[Zn])...Equation 1 (In the above formula 1, [Ag], [In], [Ga], and [Zn] are the molar contents of silver, indium, gallium, and zinc, respectively; The molar ratio of gallium to indium (Ga / In) is greater than 2.5 and less than 5.
6.
2. The semiconductor nanoparticles according to claim 1 , wherein the charge balance value of the semiconductor nanoparticles defined by the following formula 2 is 0.91 or more and 1.2 or less. [Formula 2] Charge balance value={[Ag]+3×([In]+[Ga])+2×[Zn]} / (2×[S])...Equation 2 (In the above formula 2, [Ag], [In], [Ga], [Zn], and [S] are the molar contents of silver, indium, gallium, and sulfur, respectively.)
3. The semiconductor nanoparticle according to claim 2 , wherein the charge balance value is 0.93 or more and 1.17 or less.
4. the relative molar ratio of zinc is equal to or greater than 0.28 and equal to or less than 0.66; 2. The semiconductor nanoparticles according to claim 1, wherein a molar ratio of gallium to indium (Ga / In) is 2.9 or more and 4.5 or less.
5. In the semiconductor nanoparticles, The molar ratio of zinc to indium (Zn / In) is 2.7 or more and 10.5 or less, 2. The semiconductor nanoparticles according to claim 1, wherein the molar ratio of gallium to silver (Ga / Ag) is 1.1 or more and 3 or less.
6. In the semiconductor nanoparticles, the molar ratio of gallium to the sum of gallium, indium, and silver (Ga / (Ga+In+Ag)) is 0.45 or more and 0.7 or less; The molar ratio of zinc to sulfur (Zn / S) is 0.1 or more and 0.8 or less; or 2. The semiconductor nanoparticles according to claim 1, wherein a molar ratio of the sum of indium and gallium to sulfur ((In+Ga) / S) is 0.1 or more and 0.8 or less.
7. In the semiconductor nanoparticles, a molar ratio of silver to the sum of silver, indium, and gallium (Ag / (Ag+In+Ga)) is 0.2 or more and 0.5 or less; 2. The semiconductor nanoparticles according to claim 1, wherein a molar ratio of sulfur to the sum of silver, indium, and gallium (S / (Ag+In+Ga)) is 1 or more and 2.5 or less.
8. The semiconductor nanoparticle of claim 1, wherein the semiconductor nanoparticle comprises a first particle comprising silver, indium, gallium, and sulfur, and a semiconductor nanocrystal layer comprising zinc and sulfur disposed on the first particle.
9. the emission peak wavelength of the green light is in the range of 500 nm to 580 nm, 2. The semiconductor nanoparticles according to claim 1, wherein the quantum yield of the semiconductor nanoparticles is 70% or more and 99% or less.
10. 2. The semiconductor nanoparticle according to claim 1, wherein the half-width of the semiconductor nanoparticle is 40 nm or less.
11. 2. The semiconductor nanoparticles according to claim 1, wherein the trapped emission percentage of the semiconductor nanoparticles calculated by the following formula 3 is 25% or less: [Formula 3] Trap emission percentage = [trap emission area of emission spectrum / total area of emission spectrum] × 100 ... formula 3 (In the above formula 3, the trap emission area is the peak area having a wavelength of the emission peak wavelength + 50 nm or more.)
12. A method for producing the semiconductor nanoparticles according to claim 1, comprising the steps of: reacting a zinc precursor and a sulfur precursor in the presence of first particles comprising indium, gallium, silver, and sulfur to form a semiconductor nanocrystal layer comprising zinc and sulfur on the first particles; reacting the zinc precursor with a sulfur precursor includes adding the first particles and the zinc precursor to a reaction medium including the sulfur precursor and an organic solvent; The method of claim 1, wherein the reaction is carried out at a temperature greater than 180° C. and less than 240° C.
13. the sulfur precursor comprises a thiol compound, an isothiocyanate compound, a thiourea compound, a thioacetamide compound, or a combination thereof; 13. The method of claim 12, wherein the zinc precursor comprises a Zn halide.
14. The temperature of the reaction is equal to or higher than 205° C. and equal to or lower than 215° C.
13. The method of claim 12, wherein the time for the reaction is not less than 30 minutes and not more than 2 hours.
15. 13. The method of claim 12, wherein the organic solvent comprises a mixture of an aliphatic hydrocarbon solvent having 5 to 40 carbon atoms and an amine solvent having 5 to 40 carbon atoms.
16. A composite comprising the semiconductor nanoparticles according to claim 1, The composite is characterized in that it comprises a matrix and the semiconductor nanoparticles dispersed in the matrix.
17. The composite of claim 16, wherein the composite has a relative luminous efficiency, as defined by the following formula 4, of 60% or more when maintained in air for 48 hours: [Formula 4] Relative luminescence efficiency (%) = [luminescence efficiency of the complex after 48 hours / initial luminescence efficiency of the complex] × 100 ... Equation 4
18. A color conversion structure comprising the semiconductor nanoparticles according to claim 1, the color conversion structure includes a color conversion layer including color conversion regions and partitions that optionally define each region of the color conversion layer; the color conversion area includes a first area corresponding to a first pixel; A color conversion structure, wherein the first region contains the semiconductor nanoparticles.
19. An electronic device comprising the semiconductor nanoparticles according to claim 1.
Citation Information
Patent Citations
Photosensitive compositions, preparation methods thereof, and quantum dot polymer composite prepared therefrom
US20170052444A1